A sustainable large language model predict framework for anaerobic digestion: bridging laboratory knowledge and industrial scaling - Yi Zhang; Peng Quan; Fangyun Wang; Zhixing Pan; Xinzi Wang; Hengyu Lin; Zheng Hao Leong; Jiayue Zhang; Jianfeng Peng; Yeqing Li; Zongguo Wen (Bioresource Technology, 2027)

Multiple magma sources and incremental assembly of the late Mesozoic Yunmengshan batholith, North China Craton: Constraints from zircon Hf-O isotopes and apatite geochemistry - Zi-Mu Li; Miao-Miao Ling-Hu; Shi Chen; Jin-Feng Sun; Ji-Heng Zhang; Ya-Dong Wu; Bao-Quan Zhou; Quan-Lin Hou; Jin-Hui Yang (Lithos, 2026)

Unlocking the Size-Dependent mechanism of CO2 reduction on Carbon-Supported Nin clusters - Yimeng Sun; Lin Tao; Meixu Lu; Xin Quan; Mingjie Wu; Javed Rehman; Nan Wang; Lixiang Li; Baigang An (Fuel, 2026)

Single-channel magnetotactile interface with structurally decoupled polarity–eigenfrequency encoding for in-plane sliding-direction decoding - Xiaojuan Hou; Shaowei Quan; Xin Zhang; Huipeng Zhao; Lin Shi; Fen Li; Wenping Geng; Jian He; Xiujian Chou (Chemical Engineering Journal, 2026)

Visibly transparent photoluminescent film for energy-efficient chromatic glazing - Yingxiao Li; Quan Gong; Jihong Pu; Lin Lu (Chemical Engineering Journal, 2026)

Trace metals in root-stem-leaf of mangrove communities: bioconcentration, migration and biochemical influencing mechanisms in Circum-Xinying-Bay, Hainan, China - Lin Du; Junhao Yang; Chengqian He; Jingyi Cui; Zun Teng; Quan Chen (Marine Pollution Bulletin, 2026)

Integrated network pharmacology and experimental validation to elucidate the mechanism of WIN55,212–2 in mitigating sepsis-induced pulmonary fibrosis in mice - Quan He; Dei-xing Yang; Lin Duo; Tong-ling Shi; Yuan-wei Yang; Jie-cheng Li; Shu-ting Li; Shang-shang Zhu (Tissue and Cell, 2026)

Albafurans D−N, 2-phenylbenzofuran derivatives with anti-inflammatory activity from Morus alba - Jun-Sheng Zhang; Lin-Lin Tian; Quan-Hao Wei; Meng-Jie He; Hua Zhang (Phytochemistry, 2026)

Mapping recorded illegal tree-felling intensity for forest-governance screening in China: Evidence from court verdicts and interpretable spatial machine learning - Lin Chen; Yuwei Hong; Yu Liu; Mengxue Yuan; Ximing Quan; Weixing Xue; Pujie Wei; Yingjie Liao; Zhaogui Yan (Forest Policy and Economics, 2026)

Biomimetic nanozyme-mediated domino catalysis for reprogramming energy metabolism to enhance ferroptosis against TNBC - Annan Liu; Lei Li; Ze Wang; Kejun Jiang; Hao Liang; Yiying Ding; Andrew K. Whittaker; Quan Lin (Chemical Engineering Journal, 2026)

Bamboo-Inspired bionic microfluidic Reactor: Construction and application for industrial Biocatalysis - Quan Zhou; Litao Wang; Zijing Zhao; Xi Lin; Jiandong Wang; Guosheng Liu; Zihui Cai; Chaobo Huang; Yujie Fu (Bioresource Technology, 2026)

Chemical constituents from the leaves of Yulania denudata and their chemotaxonomic significance - Zhen-Quan Li; Qiu-Ye Zhao; Hui-Ling Zhou; Shi-Huan Yin; Xuan Jiang; Xin-Ying Wang; Lu Sai; Lin-Fen Ding; Liu-Dong Song (Biochemical Systematics and Ecology, 2026)

Phylogenomics, reticulate evolution, and taxonomic revision of East Asian Cardamine (Brassicaceae) in the Hengduan biodiversity hotspot - Jia-lu Li; Dan-hui Liu; Jiang-lin Miao; Yi He; Liao-cheng Zhao; Di Zhang; Ke-ping Ma; Quan-ru Liu (Molecular Phylogenetics and Evolution, 2026)

Occurrence, variation and risks of viruses in aerosols during rural wastewater collection, treatment and discharge - Yingming Zhu; Su Xu; Yu Zhou; Ruiqi Quan; Jun Zhan; Xuesong Guo; Lin Li; Junxin Liu (Journal of Cleaner Production, 2026)

ER stress promoted MAMs formation and ER-Mito Ca2+ transfer: implication for fluoride-induced hippocampal neuronal injury and cognitive deficits in mice - Siman Lin; LuYang Cao; Yuzhe Zhou; Shengdan Liu; Yue Yan; Qiwei Zhang; Quan Yuan; Yufei Gao; Ge Du; Jun Hu; Dongmei Wang; Hua Fan (Chemico-Biological Interactions, 2026)

Geographic patterns and drivers of leaf C:N:P:K stoichiometry in mangrove forests across Hainan Island: climatic forcing overwhelms sedimentary effect - Qian Chen; Lin Du; Chengqian He; Jingyi Cui; Mengli Wang; Zhongyi Sun; Quan Chen (Hydrobiologia, 2026)

An Analysis of Growth Characteristics and Population Dynamics of Cynoglossus gracilis in the Offshore Waters of Liaoning Province, China - Lin Zhang; Yingyou Zhou; Zengqiang Yin; Qifa Zhang; Yikai Lan; Quan Yu; Jiahang Wei; Fan Du; Lei Chen (Fishes, 2026)
This study investigated the population dynamics of Cynoglossus gracilis in the offshore waters of Liaoning Province, China, to support sustainable fisheries management. Biological samples were collected from five major fishing ports between March and November 2024. Population dynamics were assessed based on growth, mortality, and exploitation parameters, and four seasonal fishing closure scenarios were evaluated using egg production per recruit (EPR) and spawning biomass per recruit (SBR) models. The estimated exploitation rate (E = 0.53) indicated that the stock was experiencing relatively high fishing pressure but remained close to the sustainable exploitation reference level. Yield-per-recruit analysis suggested that increasing the minimum catchable size could improve resource utilization efficiency. Among the evaluated closure scenarios, the April–September closure provided the greatest conservation benefit by enhancing reproductive potential and protecting spawning stock biomass. These findings provide valuable insights for optimizing harvest regulations and seasonal closure strategies, contributing to the sustainable management of Cynoglossus gracilis resources in the offshore waters of Liaoning Province.

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Data-driven surrogate modeling of underwater vehicle wake and feature inversion of navigation parameters - Jie-Lin Ren; Wei-Pei Huang; Li Wang; Yu-Quan Wang; Kai-Qi Zhao; Peng-Nan Sun (Ocean Engineering, 2026)

Comprehensive analysis of microbial community assembly and metabolic dynamics reveals the effects of environmental acidity on flavor formation pathways during the Zhejiang rosy vinegar fermentation process - Cheng-Hao Jin; Yong-Zhu Zhang; Wen-Tian Song; Peng Wang; Chang-Ling Wu; Lin-Mei Liang; Wei Feng; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Neutrophils: The Overlooked Regenerative Role in Bone Repair - Yumeng Lin; Yuchen He; Quan Yuan; Shiwen Zhang (Stem Cell Reviews and Reports, 2026)

Artificial Intelligence and Protein Design: A retrospective study on 20-year emerging trends and core research areas from bibliometric perspectives - Wenjuan Zhao; Xiuwu Pan; Wei Yang; Zichang Liu; Xiyi Wei; Anqi Lin; Bufu Tang; Lin Zhang; Mingjia Xiao; Qing Zeng; Quan Cheng; Weiming Mou; et al. (Probiotics and Antimicrobial Proteins, 2026)

Functional noncoding variants within the TBX1 enhancer contribute to tetralogy of Fallot - Jimiao Gao; Tao Jiang; Yingyi Quan; Xinyue Liu; Min Da; Jiang Jiang; Jun Zhou; Hao Sun; Yan Zhou; Wanting Ma; Zicheng Zhang; Yiwei Cheng; et al. (Science China Life Sciences, 2026)

Construction and immunogenicity evaluation of avian Escherichia coli-derived bacterial biomimetic vesicles displaying H9 subtype avian influenza virus HA1 protein - Yue Li; Yuji Quan; Keji Quan; Mengqi Lin; Peng Chen; Xiangkai Zhuge; Tao Qin; Sujuan Chen; Yuncong Yin; Daxin Peng (Veterinary Microbiology, 2026)

High-efficiency analysis of large-scale train–track–bridge systems based on a localized nonlinear stiffness decomposition method - Quan Gu; Zhe Lin; Jinghao Pan; Yingpeng Tang; Wei Guo (Soil Dynamics and Earthquake Engineering, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

Synergistic effects between Si, Cu and K promoters and their influences on the structures and performances of Fe-based Fischer–Tropsch synthesis catalysts - Xiaoming Suo; Zhengjia Li; Jie Cen; Meng Cheng; Quan Lin; Zhuowu Men; Weizhen Li; Nan Yao; Xiaonian Li (Fuel, 2026)

From microbial succession to precision fermentation: Enhancing Yunnan coffee flavor with a defined native yeast starter guided by multi-omics - Chenxi Quan; Zhouwei Wu; Guilin Hu; Xiaocui Liu; Yuancao Shu; Xingrong Peng; Lin Zhou; Wenyong Xiong; Minghua Qiu (Food Research International, 2026)

Cessation of nitrogen addition maintains higher soil organic carbon stability in a subtropical forest acid soil - Quan Li; Tingting Cao; Shuangbo Bi; Mianhai Zheng; Qiqian Wu; Wenjuan Yu; Man Shi; Zhikang Wang; Yuchen Lin; Yakov Kuzyakov; Xinzhang Song (CATENA, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Comparative analysis of chemical compositional profiles and immunomodulatory activity of ginseng in different habitats - Chen-Yue Zeng; Quan-Kuan Dai; Hua-Ze Wu; Ao Li; Yong-Lin Chen; Qing-Hui He; Dan Tang; Hong-Yan Ma (Journal of Natural Medicines, 2026)

Vegetation, treeline and peatland evolution on the eastern Tibetan Plateau over the past two millennia - Weihe Ren; Yang Lin; Cai Liu; Guitian Yi; Yuqi Wu; Chen Liang; Quan Li; Feng Qin (Vegetation History and Archaeobotany, 2026)

Analyzing seasonal and nonlinear built environment-energy dynamics using street view imagery in New York City - Qi Lin; Yichun Zhou; Steven Jige Quan; ChengHe Guan (Sustainable Cities and Society, 2026)

Genesis of copper-deficient skarn iron deposits in the North China Craton: Insights from apatite and whole-rock geochemistry - Jun-Wu Zhang; Lin Li; Ju-Quan Zhang; Fang-Yue Wang; Xian Liang (Journal of Geochemical Exploration, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Enhancing urban river self-purification through riverbed substrates configuration: A nature-based solution for nutrient removal and restoration planning - Yu Xin; Lin Liu; Shao-Hua Chen; Quan-Bao Zhao; Yu-Ming Zheng (Journal of Environmental Sciences, 2026)

A new sesquiterpene lactone and other phytochemicals from the fruits of Magnolia grandiflora and their chemophenetic significance - Qiu-Ye Zhao; Zhen-Quan Li; Shi-Huan Yin; Hui-Ling Zhou; Xin-Ying Wang; Wei-Yang Feng; Lin-Fen Ding (Biochemical Systematics and Ecology, 2026)

Tracing the evolution of granitic magmas revealed by fayalite–ferrosilite-bearing microgranular enclaves in Jiuyishan area of South China Block - Jing-Yi Liu; Quan Ou; Jian-Qing Lai; Feng Zi; Kun Wang; Wen-Zhou Xiao; Zhi-Cheng Lin; Cui-Yun Wang; Qian-Cheng Feng; Jia Liao (Acta Geochimica, 2026)

PCGF1 is a key factor for facilitating dynamic H3K27me3 modification during early lineage specification - Pan Chen; Xuejie Yang; Ruhai Chen; Hanlu Li; Jingwen Ma; Jing Chang; Guangliang Hong; Wei Liu; Xiongzhi Quan; Bin Yin; Lin Hou; Boqin Qiang; et al. (Science Bulletin, 2026)

RACS: A region-adaptive categorical similarity kernel for surrogate modeling with mixed-variable problems - Qianxu Wu; Xinglong Xia; Quan Lin; Tingli Xie; Qi Zhou (Ocean Engineering, 2026)

Deficiency of TEX264-mediated reticulophagy is linked to ER stress-induced neuronal necroptosis: Implication of fluoride-associated hippocampal injury and cognitive dysfunction - Ge Du; Quan Yuan; Rui Liu; Jiaming Liang; Milan Yang; Yufei Gao; Xiaoli Liu; Siman Lin; Rui Zhang; Binbin Wang; Dongmei Wang; Hua Fan (Journal of Environmental Sciences, 2026)

A high-performance bimodal sub-nanoporous polyelectrolyte complex membrane for organic solvent nanofiltration constructed by MOF-reinforced nano-unit - Hui-Qian Huo; Bing-Xin Gu; Jin-Lin Wang; Jia-Chen Zhang; Kai Zhang; Ming-Jie Yin; Yan-Li Ji; Quan-Fu An (Chemical Engineering Journal, 2026)

QD394 induces ferroptosis and suppresses the proliferation of colorectal cancer via the SP1/JNK pathway - Ruixue Zhang; Haiyan Quan; Wenjing Xiao; Zhenhua Lin; Aihua Jin (Apoptosis, 2026)

Structurally diverse sesquiterpenoids from the fruits of Magnolia grandiflora Linn. and their cytotoxic activities - Qiu-Ye Zhao; Jin-Da Li; Shi-Huan Yin; Zhen-Quan Li; Hui-Ling Zhou; Jia-Qing Feng; Wei-Yang Feng; Xing-De Wu; Lin-Fen Ding (Phytochemistry, 2026)

Apportioning nitrate sources via dual isotope, PMF and SIAR in a complex urban river network during flood season: Implications for engineered mitigation strategies - Xin Wang; Qiaoyun Lin; Zhixiong Huang; Yihua Cai; Wenjing Wang; Nan Rong; Siye Wei; Renren Wu; Quan Zhou (Journal of Water Process Engineering, 2026)

Microbial community-driven cadmium activation in high-geochemical background soils by small-sized PBAT microplastics - Lijuan Cha; Ruiyao Shi; Yafeng Wang; Rongrong Lin; Zhiyun Zhang; Pengfei Wang; Min Wu; Quan Chen; Bo Pan (Journal of Hazardous Materials, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Effects of baking degree of Longjing green tea on flavor attributes, antioxidant activity and advanced glycation end products - Ran Wei; Xiao-Yu Zhong; Kayama Kayama; Yu-Hong Lin; Fang-Ting Qin; Zhu-Cheng Su; Yong-Quan Xu (Food Research International, 2026)

Fabrication of extracorporeal mechanical energy harvesting and implantable triboelectric nanogenerators for self-powered medical devices - Zhenni Liu; Hu Bian; Cong Lin; Quan Chen; Jia Liu; Zhenming Chen; Jun Chen; Dongdong Fang; Junjun Huang (Chemical Engineering Journal, 2026)

Electromyographic features for quantitative assessment of lower limb spasticity after stroke: a feasibility study - Lin Wu; Benjian Zou; Jiawei Liu; Chao Wang; Samit Chakrabarty; Ping Zhou; Tianzhe Bao; Sheng Quan Xie (Medical & Biological Engineering & Computing, 2026)

Coupled Effects of Reservoir Level Fluctuations and Rainfall on Landslide Deformation Using InSAR and DEM Analysis - Liu Tie-biao; Liu Ming-quan; Luo Shi-lin; He Kun-lin; Yan Guang-zhi; Chen Guo-feng; Cao Su-ting (Geotechnical and Geological Engineering, 2026)

Retraction Note: Nexus between agro-ecological efficiency and carbon emission transfer: evidence from China - Usman Akbar; Quan-Lin Li; Muhammad Abdullah Akmal; Mohammed Shakib; Wasim Iqbal (Environmental Science and Pollution Research, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

Corrigendum to “Grazing practices affect phyllosphere and rhizosphere bacterial communities of Kobresia humilis by altering their network stability” [Sci. Total Environ. 900 (2023) 165814] - Jin-Peng Hu; Ming-Xu Zhang; Zhao-Long Lü; Yuan-Yuan He; Xiao-Xia Yang; Xiang-Ling Fang; Quan-Min Dong; Jin-Lin Zhang (Science of The Total Environment, 2026)

Multi-scale drivers shaped the late Quaternary vegetation composition in eastern Nanling Mountains, subtropical China - Mingying Quan; Wei Zhong; Xiaojun Wang; Tianhang Li; Durui Lin; Limi Mao (Quaternary Science Reviews, 2026)

Endoplasmic reticulum stress-induced CHOP activation mediates NLRP3 inflammasome-dependent pyroptosis in BDE-47-induced cognitive dysfunction - Quan Yuan; Rui Zhang; Jun Hu; Siman Lin; Ying Zhu; Junhong Geng; Ge Du; Xiao Yang; Yipin Zhao; Dongmei Wang; Binbin Wang; Hua Fan (NeuroToxicology, 2026)

Seasonal variation regulates the efficacy of phytoremediation strategies on the rhizosphere resistome in urban river ecosystems - Yu Xin; Li-Hua Liu; Lin Liu; Shao-Hua Chen; Yu-Ming Zheng; Quan-Bao Zhao (Journal of Hazardous Materials, 2026)

Isolation and identification of spoilage bacteria from kiwifruit and analysis of the antagonistic activity of three Bacillus strains against these bacteria - Ang Liu; Wen-xin Li; Yi Liu; Xing-lin Ran; Bo-yu Dong; Qiu-ping Yao; De-quan Zhu (Food Control, 2026)

From farm to table: The statuses, hotspots, and trends on research of HACCP application in global food supply chains (1990–2025)—A bibliometric analysis based on CiteSpace - Jiuhao Chen; Junfei Chen; Yuze Guan; Shijie Xue; Yinqiang Liu; Yifan Guo; Shisheng Zhu; Shiyu Quan; Tianci Lin; Zhihao Ni (Food Control, 2026)

BMSC vesicles-encapsulated tannic acid-derived carbon dots efficiently target and orchestrate mitochondria mitophagy to promote cartilage repair in osteoarthritis - Rongjie Lin; Zhusong Huang; Weibin Chen; Quan Liu; Huiling Guo; Xingyu Lin; Yao Wang; Zhenbin Chen; Xi Zeng; Shishui Lin; Shaohuang Weng; Min Chen (Chemical Engineering Journal, 2026)

Preferential N2-transport thin-film composite membrane for energy-efficient CO2 capture - Jin-Lin Wang; Cheng-Gang Jin; Hui-Qian Huo; Bing-Xin Gu; Yue Li; Wen-Hai Zhang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2026)

Alpha-ketoglutarate restores oral epithelial homeostasis via FOXM1-mediated cell cycle regulation - Yuan Wang; Yimeng Cai; Qi Yin; Shuqin Cao; Yuyu Li; Yuhan Li; Qiwen Li; Qian Wang; Pochun Lin; Li Mei; Malcolm Xing; Leixiao Yu; et al. (Science China Life Sciences, 2026)

Phylogeographic Pattern and Genetic Structure of the Cyprinid Fish Microphysogobio kachekensis (Oshima 1926) in Mainland China and Hainan Island Based on Mitochondrial and Nuclear DNA - Jin-Quan Yang; Jiabo Chen; Junjie Wang; Tian-Qi Zhou; Yuh-Wen Chiu; Hung-Du Lin; Wen-Sheng Ou (Fishes, 2026)
South China’s freshwater biodiversity has been shaped by Quaternary climatic oscillations and persistent geological barriers. We investigated the phylogeography and conservation implications of the primary freshwater fish Microphysogobio kachekensis across mainland China and Hainan Island using mitochondrial (cyt b and control region) and nuclear (RAG2 and rpS7-1) markers from 200 individuals. Mitochondrial analyses recovered two major lineages and multiple sublineages largely structured by drainage basins, whereas nuclear data resolved four geographically concordant lineages. Population differentiation was strong (high FST), and SAMOVA/AMOVA supported major barriers restricting gene flow, including the Qiongzhou Strait, Gulf of Tonkin, Yunkai Mountains, and Nanling Mountains. Ancestral-area reconstruction inferred the Pearl River region as the most likely source area, followed by dispersal to northern Hainan and subsequent expansion to southern Hainan and the Red River, with additional northward expansion to the Zhejiang–Fujian region. Despite high haplotype diversity, within-population nucleotide diversity was low, consistent with long-term river isolation and complex demographic history. We propose six ESUs and four MUs for evolutionarily informed conservation and to guide stock enhancement in southern China.

Sediment physicochemistry outweighs anthropogenic factors in driving sediment heavy metals accumulation within mangrove forests across Hainan Island, China - Mengli Wang; Lin Du; Qian Chen; Zhongyi Sun; Quan Chen (Marine Pollution Bulletin, 2026)

Complex variable solution for multi-step shallow tunnel excavation considering gravitational effects - Luo-bin Lin; Fu-quan Chen; Chang-jie Zheng; Shang-shun Lin (Tunnelling and Underground Space Technology, 2026)

Integrated transcriptomic and metabolomic analyses reveal the molecular adaptive mechanisms of Schizopygopsis chengi baoxingensis under acute heat stress - Hangyu Lin; Xiaoyun Wu; Ya Liu; Jun Ou; Luyun Ni; Feiyang Li; Jiansheng Lai; Quan Gong; Jue Lin; MingJiang Song (Journal of Thermal Biology, 2026)

Insight into the internal microscopic structure and composition of aerobic granular sludge under high salinity based on high-resolution Micro-CT technology - Yuhao Tong; Aqiang Ding; Jun Liu; Lin Quan; Hao Liu; Fuzhong Song; Demin Yang; Daijun Zhang; Peili Lu (Environmental Research, 2026)

Unraveling the critical role of nanoplastics in governing the interfacial behavior and toxicity evolution of ciprofloxacin during Fenton oxidation process - Hanjun Zhu; Haishuai Cui; Guopei Huang; Hai Yang; Jukun Xiong; Meimei Ran; Xiaoping Lin; Quan Wan; Lele Yang; Zelin Xu; Xin Nie (Chemical Engineering Journal, 2026)

A targeted therapy for salivary adenoid cystic carcinoma: A homologous bimetal nanoplatform via the cGAS-STING-mediated immunostimulation - Shaofeng Liu; Quan Zheng; Jingju Yin; Yue Huang; Gengsen Zou; Kun Song; Qi Lin; Jinxia You; Yunyang Liao; Bin Shi (Chemical Engineering Journal, 2026)

Microbial mechanisms of arbuscular mycorrhizal fungi in mitigating nitrous oxide emissions via regulating nitrogen metabolism in constructed wetlands - Xiang-Long He; Liang-Cheng Lin; Yi-Hao Li; Yu-Quan Zhong; Hao Xu; Jing-Wen Li; Can Liu; Jun-Feng Wang (Chemical Engineering Journal, 2026)

Low phosphorus promotes caryophyllene biosynthesis by regulating AaTPS3 in Artemisia argyi - ZhongWen Ma; Ping Lu; Quan Gu; ShiMin Zhang; ZhiYuan Feng; YongPing Cai; Lin Liu (Plant Cell Reports, 2026)

Ripened Pu-erh tea modulates the gut microbiome to enhance metabolic homeostasis and redox-inflammatory balance: A systematic review of core health benefits and mechanisms - Ming Zhao; Teng Wang; Lin Zeng; Qiuyue Chen; Dihan Yang; Yiqing Guan; Nianguo Bo; Yong-Quan Xu; Yan Ma (Trends in Food Science & Technology, 2026)

Mechanisms driving anammox bacteria enrichment in constructed wetlands for self-purification of high-nitrogen polluted wastewater: Environmental gradients and microbial interactions - Lin Liu; Jie Li; Yu Xin; Quan-Bao Zhao; Yu-Ming Zheng (Journal of Environmental Sciences, 2026)

A novel aqueous synthesis of anion exchange membranes for fuel cells - Xia Liu; Zhongshan Feng; Cuiwen Deng; Quan Yang; Minhao Wang; Xinjie Zhang; Yi Hu; Yufan Zheng; Juan Zeng; Bencai Lin; Juanjuan Han (Fuel, 2026)

Amplifying 2′3′-cGAMP with “open source throttling” strategy: Intelligent nanoreactors enhance immunotherapy in HNSCC via cascade activation of the cGAS-STING pathway - Tong Sha; Ze Wang; Jinwei Li; Yahong Wu; Xiaoyi Yu; Jinbiao Qiang; Annan Liu; Hao Liang; Zunxuan Xie; Yijun Zhou; Hongchen Sun; Andrew K. Whittaker; et al. (Chemical Engineering Journal, 2026)

Mechanisms of bioelectrochemistry enhanced saline aerobic granular sludge: From EPS monomers to microbial metabolism - Aqiang Ding; Shikang Li; Wenkai Yao; Yuhao Tong; Lin Quan; Chun Yang; Fuzhong Song; Daijun Zhang; Peili Lu (Chemical Engineering Journal, 2026)

Screening and In Vivo Validation of Key Genes Involved in Myelin Damage in Alzheimer’s Disease - Hai-Tao Li; Ji-Wei Zhang; Bo-Wen Li; Hong-Yun Wu; Jin-Wen Ge; Da-Hua Wu; Quan-Lin Zhao; Ya-Han Wang (Molecular Neurobiology, 2026)

Phillyrin promotes flap survival by mitigating pyroptosis through the TLR4/NF-κB/NLRP3 signaling pathway - Jiapeng Deng; Wenrui Kang; An Wang; Jialong Yang; Kaitao Wang; Lekai Quan; Hebin Pan; Weilong Song; Panshen Xu; Dingsheng Lin (Apoptosis, 2026)

Exploring the complexities of bitterness: a comprehensive review of methodologies, bitterants, and influencing factors centered around coffee beverage - Gui-Lin Hu; Jameel Hizam Alafifi; Chen-Xi Quan; Abdulbaset Al-Romaima; Ming-Hua Qiu (Critical Reviews in Food Science and Nutrition, 2025)

AFP-GFuse: an antifungal peptide identification model with structural information fusion via multi-graph neural networks and cross-attention mechanism - Xiaomeng Lin; Ruiqi Liu; Aoyun Geng; Junlin Xu; Yajie Meng; Feifei Cui; Leyi Wei; Quan Zou; Zilong Zhang (Molecular Diversity, 2025)

A unified framework for predicting vertical bearing capacity of fully embedded pipes/tunnels in clay seabed based on the undrained failure mechanisms - Yu Zhao; Xing-Tao Lin; Wei-Jian Li; Jun-Chen Zhang; Zhi-Yao Tian; Quan-Mei Gong (Ocean Engineering, 2025)

Linking nature-based hydrodynamic redesign to ecological feedback in urban channelized rivers: A 3D modeling-metagenomic integration framework - Yu Xin; Lin Liu; Xin Ye; Shao-Hua Chen; Yu-Ming Zheng; Quan-Bao Zhao (Journal of Hydrology, 2025)

A systematic review of concrete self-healing mechanism and analysis of new research directions - Quan Xue; Xianlei Feng; Yumeng Sun; Zheng Si; Liwei Zhang; Zhenhua Zhou; Yu Zhong; Kaiyuan Mei; Guanghua Lin; Huiyizhe Zhao (Journal of Environmental Chemical Engineering, 2025)

Advances in the research on phenolic acids and flavonoids in vinegar: Sources, formation and degradation mechanisms, and functional properties - Cheng-Hao Jin; Yong-Zhu Zhang; Feng-Hua Wu; Chang-Ling Wu; Peng Wang; Wei Feng; Lin-Mei Liang; Wei-Jiang Xu; Xiao-Tao Sun; Xing-Quan Liu; Guan-Yu Fang (Food Research International, 2025)

Fabrication of Rubus chingii Hu ellagitannins-loaded W/O/W double emulsion gels stabilized by WPI/pectin complexes: Physicochemical properties, digestion characteristics, and transformation of ellagitannins - Dong-Jun Hou; Quan-yuan Xie; Ming-Shun Chen; Yu-Lin Cheng; Bing Zhang; Zong-cai Tu; Lu Zhang (Food Chemistry, 2025)

Establishment of a cobia (Rachycentron canadum) gill cell line: a valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Flexible solar evaporator for simultaneous desalination and VOCs removal from seawater - Long-Feng Hu; Huiting Zhang; Huan Lin; Hui Niu; Hao-Ran Chen; Quan-Fu An (Chemical Engineering Journal, 2025)

Machine learning coupling microbial succession to decipher gas stripping-reinforced sulfate reduction for hydrogen sulfide removal - Ting-Ting Zhang; Ei Myat Mon Oo; Bi-Long Chen; Lin Liu; Quan-Bao Zhao; Jia-Cheng E. Yang; Yu-Ming Zheng (Bioresource Technology, 2025)

Gut microbiome-targeted therapeutics for chronic kidney disease: comparative efficacy of probiotic and microbial preparations - Yi-Ke Li; Wen-Ru Li; Huan Ren; Chen-Lin Xiao; Zhen Guo; Jian-Quan Luo (Inflammopharmacology, 2025)

Identification of the Q-type ZFP gene family in Triticeaes and drought stress expression analysis in common wheat - Pengyan Guo; Changyan Cui; Baoquan Quan; Jiping Zhao; Jingna Ru; Yanzhen Wang; Zhiyuan Song; Aohui Lin; Shuwen He; Guanghao Wang (Genetica, 2025)

β-Lapachone sensitizes glioblastoma to Temozolomide by inhibiting NF-κB signaling - Chunhua Quan; Ying Liu; Yuan Gao; Houkun Zhou; Haiyan Quan; Anna Han; Xiaodan Lu; Zhenhua Lin (Functional & Integrative Genomics, 2025)

Modulation of growth, gut-liver axis, and antioxidant defense by Bacillus tequilensis (GCB-3) in grass carp (Ctenopharyngodon idella) under high-carbohydrate diet: Insights into health enhancement and oxidative stress mitigation - Xin Wang; Dongming Zhang; Xinping Zhang; Xinyu Lei; Dan Jiang; Lili Lin; Wenli Zhu; Sibu Wang; Quan Huang; Yuxin Li; Yu-ke Chen; Zhixin Guo (Animal Feed Science and Technology, 2025)

Effects of dietary alpha-ketoglutaric acid on growth performance and intestinal barrier function in Lateolabrax maculatus fed a high soybean meal diet - Fuqiang Quan; Jianrong Ma; Yanbo Zhao; Hao Lin; ZhongBao Li (Aquaculture International, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Overlooked synergisms of flotation organic reagents and toxic metals in water: Formation of tridentate cadmium-xanthate complexes - Lei Xiang; Qian-Wen Wang; Wen-Jun Wu; Nian-Jue Zheng; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; Qing X. Li (Water Research, 2025)

Rapid and efficient stem segment regeneration propagation system for Euonymus bungeanus - Kai-Ge Cui; Hao-Lin Wang; Wen-Yue Quan; Zhuo-Zhuo Ye; Cheng-Ri Zhao (South African Journal of Botany, 2025)

Ensemble atomic sites for acidic oxygen evolution: mechanisms, atomic engineering, and AI-assisted screening - Wenjia Qu; Xingen Lin; Handuo Zheng; Jianuo Liu; Cheng Qian; Kong Chen; Huang Zhou; Yafei Zhao; Quan-Hong Yang; Yuen Wu (Science Bulletin, 2025)

Community and functional succession of corrosive microorganisms during flowback and produced water management in Sichuan Basin - Jiayi Qing; Aqiang Ding; Zhengming Hou; Lin Quan; Yuhao Tong; Junou Pan; Xiong Li; Peili Lu (Journal of Water Process Engineering, 2025)

Synergistic effects of biochar and E. coli on reducing cadmium bioavailability and improving soil fertility through enhanced bacterial-fungal interactions - Quan Chen; Rongrong Lin; Wan-Rong Zhang; Yafeng Wang; Yanqing Xiong; Pengfei Wang; Yu Huang; Min Wu; Peng Yi; Bo Pan (Journal of Hazardous Materials, 2025)

Grazing accelerates soil carbon loss by enhancing the degradability of soil water-extractable organic matter and microbial turnover in fragile grasslands - Hao Chen; Liwen Lin; Quan Shi; Jianshuang Wu; Fei Wang; Mukan Ji; Qimei Lin; Xianzhou Zhang; Yong-Guan Zhu; Chao Liang; Weidong Kong (CATENA, 2025)

Food-derived bioactive peptides: health benefits, structure–activity relationships, and translational prospects - Hongda Chen; Jiabei Sun; Haolie Fang; Yuanyuan Lin; Han Wu; Dongqiang Lin; Zhijian Yang; Quan Zhou; Bingxiang Zhao; Tianhua Zhou; Jianping Wu; Shanshan Li; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

A numerical study on dynamic flow past two tandem porous circular cylinders near a moving wall at Reynolds number of 150 - Hoang Quan Nguyen; Pramudita Satria Palar; Lavi Rizki Zuhal; Jhe-Kai Lin; Viet Dung Duong (Advances in Water Resources, 2025)

The Interplay of Traits, Phylogeny and Abundance Shapes Spatial Mammal Diversity Patterns - Kay Zin Than; Alice C. Hughes; Lin Wang; Zaw Zaw; Rui‐Chang Quan (Global Ecology and Biogeography, 2025)
Aim Terrestrial mammal communities are crucial indicators of tropical ecosystem health and sustainability. However, the role of shared species responses driven by functional traits and phylogenetic relatedness in shaping community assembly remains underexplored for identifying conservation hotspots. Spatial predictions of species diversity also remain limited by approaches that fail to jointly account for species occupancy and abundance. This study evaluates trait‐ and phylogeny‐informed environmental filtering in structuring mammal communities and maps spatial diversity patterns by integrating species occupancy and abundance across spatial–temporal scales. Ultimately, areas of high mammal diversity reflecting underlying assembly processes are identified to guide regional conservation planning. Location Myanmar and China. Time Period 2015–2021. Major Taxa Studied Terrestrial mammals. Methods We deployed 936 camera traps over 6 years across Upper Myanmar and Xishuangbanna, China, using a nested sampling design that ensured robust spatial–temporal replication, and analysed the data using community hierarchical models. Results Climate and habitat factors predominantly drive species richness, while traits and phylogenetic relatedness jointly shape distinct community patterns. Seasonal variation in local diversity underscores the role of environmental filtering in structuring mammal communities across space and time. Large‐bodied omnivores favour stable temperature niches, whereas reduced precipitation filters communities towards wide‐ranging mammals. Anthropogenic disturbances and forest cover loss alter community structure, diminishing the prevalence of carnivorous traits. Predictive community maps with uncertainty estimates guide future survey efforts through a more integrative, data‐informed approach to regional planning. Main Conclusions This study presents a novel framework for improving climate‐ and habitat‐based biodiversity models by integrating trait‐ and phylogeny‐informed assembly processes with abundance‐based predictions across suitable habitats. The findings, including phylogenetically clustered niches in Cervidae and Felidae, suggest that shared evolutionary adaptations, such as temperature tolerance in ungulates and disturbance tolerance in carnivores, shape community assembly under varying environmental pressures and can inform spatial conservation prioritisation.

Bio-driven Fe bond restructuring in bio-iron systems enhances electron transfer for chain elongation - Quan Liao; Lianpeng Sun; Huanzhong Deng; Siru Zhou; Mingxuan Li; Xinzhe Zhu; Chao Yang; Xiao-yan Li; Lin Lin; Ruo-hong Li (Water Research, 2025)

Scalable, durable MOF@PEI-based nanofiber membrane for efficient synergistic removal of Cr(VI) in wastewater - Jun Gao; Ze Mao; Dengbing Wang; Yuan Chen; Hanlei Lin; Jiongsheng Song; Dingsheng Wu; Shen Li; Guochen Bian; Zhenyu Li; Quan Feng (Journal of Environmental Chemical Engineering, 2025)

A critical review of oxygen supply and control strategies in single-stage partial nitritation-anammox system for autotrophic nitrogen removal from wastewater - Sha Wu; Fei Gao; Chengcheng Lin; Yijie Quan; Yanxiao Wei; Zhihua Liu; Hanbo Yu; Eli Hendrik Sanjaya; Mohd Fadhil Md Din; Hong Chen (Journal of Environmental Chemical Engineering, 2025)

Radiative cooling rooftop systems for energy-efficient temporary housing: A Hong Kong case study - Quan Gong; Jianheng Chen; Lin Lu (Energy and Buildings, 2025)

Bio-jet production over NiFe/C bimetallic catalyst under solvent-free and low hydrogen pressure - Quan Yao; Dechao Wang; Kaiyue Wu; Jian Lin; Xin Lin; Haihan Huang; Qianyu Fan; Yankun Wu; Jinyi Duan; Jie Zheng; Yueyuan Ye; Duo Wang; et al. (Chemical Engineering Journal, 2025)

Functionalized nanohydrogel for accelerated skin burn repair with photo-activated bacteria elimination and pro-regenerative protein loading - Jian Wang; Quan Chen; Zhang Lin; Deteng Zhang; Lu Zhang; Tian-Yi Qin; Zhao-Hui Wang; Ya-Long Wang; Ming-Qiang Zhu (Chemical Engineering Journal, 2025)

Senegenin ameliorates diabetic encephalopathy via promoting mitophagy and repressing NLRP3 inflammasome activation - Xiao-dan Yan; Yu Yang; Wan-ting Zhang; Qing-quan Kong; Xi-tong Zheng; Lin-sen Li; Qing Yu (Psychopharmacology, 2025)

Perfluorooctane sulfonate (PFOS) promotes transformational transfer of antibiotic resistance genes and cross-resistance between antibiotics and PFOS - Hui Zhao; Hai-Ming Zhao; Feng Wu; Bai-Lin Liu; Hui Li; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; Ce Hui Mo; Qing X. Li (Water Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Olfactory dysfunction induced by pesticides: Adverse outcomes, emerging mechanisms, and risk for neurodegenerative diseases - Lin Wang; Si-Yang Liu; Han-Yue Zheng; Shou-Min Fang; Li Zhuo; Feng Xu; Quan-You Yu (Pesticide Biochemistry and Physiology, 2025)

Enrofloxacin drives the ultra-selective enrichment of Ca. Kuenenia stuttgartiensis under microaerobic conditions - Jiaqi Zhang; Hao Zhang; Zhenyi Ma; Lin Zhou; Qi Zhang; Quan Zhang; Chuan Chen; Rong Li; Xiao-Ming Ji (Journal of Hazardous Materials, 2025)

Dynamic changes in metabolites during the manufacture of three distinct flavor types of Tieguanyin - Lin Zeng; Yan-Qing Fu; Jin-Long Liu; Yuan-Chao Li; Shui-lian Gao; Ying Gao; Fang Wang; Yong-Quan Xu (Food Chemistry, 2025)

Identifying Key Plasma Proteins in the Onset of Parkinson’s Disease: Proteome-Wide Mendelian Randomization and Single-Cell RNA Sequencing Analysis - Wei Quan; Lin Wang; Jing Xu; Jia Song; Yidan Qin; Huibin Zeng; Jia Li; Jiajun Chen (Molecular Neurobiology, 2025)

Two new cadinane-type sesquiterpene glycosides from Dendrobium findleyanum - Zi-Xi Lin; Zhong-Quan Cheng; Dan Yang (Natural Product Research, 2025)

Response of black tea powder and its fermentation products on growth performance, antioxidant capacity, and gut microbiota of Cherax quadricarinatus - Xian-Jing Zhang; Jiao-Fen Lin; Cheng-Jian Wu; Jie-Quan Xie; You-Shu Cai; Xu-Yin Lin (Frontiers in Marine Science, 2025)
Introduction The overuse of antibiotics in aquaculture has raised concerns, necessitating the exploration of sustainable alternatives. This study evaluated tea-derived additives as potential substitutes. Methods This study evaluated the effects of black tea powder (BTP) and black tea powder-probiotics mixed fermentation product (TPMFP) on Cherax quadricarinatus growth, antioxidant capacity, and gut microbiota. Cherax quadricarinatus were fed diets supplemented with BTP (1–6%) or TPMFP (2%) for 84 days. Results The addition of BTP (<2%) to the feed enhances the weight, carapace length, and muscle protein content of Cherax quadricarinatus , while higher doses (>3%) showed adverse effects. Moreover, the addition of BTP (1%-6%) can significantly reduce the muscle content of CHO, TG, and HDL (P<0.05). The TPMFP group exhibited the highest muscle protein content and significantly elevated hepatopancreatic SOD, GSH-PX, and AKP activities (P < 0.05), indicating improved antioxidant capacity. Gut microbiota analysis revealed dose-dependent shifts, with Proteobacteria dominating (>70%) and Aeromonas increasing with BTP levels. TPMFP significantly increased the α-diversity indices (richness and evenness) of the gut microbiota. The Mantel test confirmed the relationship between the antioxidant function of the microbial community, with Proteobacteria positively correlated with GSH-PX/SOD, while Fusobacteria and Tensionella negatively correlated with antioxidant enzyme activity. Discussion This study provides a foundation for using tea-derived additives as a sustainable alternative to antibiotics in aquaculture.In the future, metagenomic analysis of key metabolic pathways can be combined to optimize the mechanistic explanation of the application and efficacy of BTP and TPMFP.

Microbial community structure and functional characteristics in shale gas flowback water from marine shale formation in Sichuan Basin, China: Insights into C-N-P-S cycle and correlations - Lin Quan; Aqiang Ding; Jun Liu; Yuhao Tong; Jiayi Qing; Junou Pan; Xiong Li; Bin Lei; Daijun Zhang; Peili Lu (Journal of Water Process Engineering, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Photochemical transformation of benzalkonium chloride in seawater - Quan Lin; Xiaokun Fu; Wenhao Jia; Guining Lu; Xingcai Chen; Kaibo Huang; Xueqing Zhou; Yini Ma (Journal of Hazardous Materials, 2025)

Unique Chain-Growth and oxygen removal mechanisms in Fischer-Tropsch synthesis on the ε-Fe2C (1–21) Surface: Insights from DFT calculations and microkinetic modeling - Huabo Zhao; Quan Lin; Hong Jiang; Yijun Lv; Zhuowu Men (Fuel, 2025)

Unlocking the healing power of Jinhua white tea fermented by Eurotium cristatum using the unique “flowering” technology: A promising ally against inflammatory bowel disease - Yong Lin; Xirui Zhou; Silin Xie; Jian-an Huang; Jie Li; Yanyan Yao; Maiquan Li; Jiahui Bo; Lizheng Xiao; Zhonghua Liu; Wei Quan (Food Research International, 2025)

Updated insights into steady-modified anthocyanin food packaging: Novel strategies, characterization, application and future challenges - Jia-Yin Huang; Yu-Lei Chen; Duan-Quan Lin; Le-Chang Sun; Kang Liu; Ling-Jing Zhang; Ya-Qin Hu; Min-Jie Cao (Food Chemistry, 2025)

NaOH-assisted heat curing towards highly permeable, superior selective, and antifouling TFC nanofiltration membranes - Weiwei Huang; Xiaozhen Lu; Wenzong Zhou; Weiwei Lv; Quan Yuan; Hang Yang; Xinwei Kang; Daoji Wu; Lin Wang; Xuewu Zhu (Desalination, 2025)

Intelligent responsive nanosystem for precision targeting and multimodal imaging-guided high-efficient photothermal therapy against colon cancer - Lei Li; Annan Liu; Hao Liang; Xingchen Li; Maja D. Nešić; Hui Guo; Ze Wang; Quan Lin (Chemical Engineering Journal, 2025)

Multi-functional transparent wood: A novel approach to balance rigidity and sensitivity in smart materials - Liangke Lin; Qi Quan; Qi Wang; Xiaoyan Zhou; Minzhi Chen (Chemical Engineering Journal, 2025)

Icing monitoring technology and application of 10 kV overhead distribution lines based on axial tension measurement - Lin Yang; Lulu Mei; Haochen He; Quan Liu; Yanpeng Hao; Licheng Li; Xinhao Lin (Cold Regions Science and Technology, 2025)

Females adapted better than males in Populus deltoides to simulated nitrogen deposition - Fang He; Shu-Ying Wei; Rui-Quan Wang; Jia Yao Tang; Peng Yang; Ting Wang; Jin-Liang Huang; Gang Chen; Tian-Tian Lin (Plant and Soil, 2025)

The potential effects of inulin on lipid metabolism disorders in spotted sea bass (Lateolabrax maculatus) induced by a high-fat diet - Fuqiang Quan; Xiujuan Wang; Zhangfan Huang; Lumin Kong; Yi Lin; Hao Lin; Sishun Zhou; Jianrong Ma; Yanbo Zhao; Yunting Zhao; Longhui Liu; ZhongBao Li (Aquaculture, 2025)

Novel n-alkanes records reveal organic matter sources and monsoon hydroclimatic changes in Dahu Swamp in South China since the last deglaciation - Wei Zhong; Xiaojun Wang; Yingbing Lin; Tianhang Li; Durui Lin; Yongdong Zhang; Mingying Quan (Quaternary Science Reviews, 2025)

Recovery and regeneration of ternary cathode materials through Solid-State reactions - Tiantian Lin; Ketai Ren; Honglai Liu; Quan Li; Cheng Lian; Jingkun Li (Chemical Engineering Journal, 2025)

Implicit Difference Solution for One-Dimensional Consolidation of Unsaturated Soil: Numerical Verification and Application to Soil-Cushion System - Qian He; Quan Yuan; Lin Lang; Jixing Cao (Mathematical Geosciences, 2025)

Early miocene adakitic porphyries in the Chagai arc, Pakistan: Petrogenesis, tectonic setting and implications for porphyry Cu-Au mineralization - Xiu-Quan Miao; Chuan-Dong Xue; Xue-Ping Yang; Yun-Ying Zhang; Jian-Lin Chen (Lithos, 2025)

Corrigendum to “Investigation of seasonal variations in submarine groundwater discharge using radium isotopes under drought conditions in northwestern coastal Taiwan” [J. Hydrol. 649 (2025) 132450] - Minh-Quan Dang; Feng-Hsin Hsu; Chih-Chieh Su; Shih-Jung Wang; Ching-Chou Fu; In-Tian Lin (Journal of Hydrology, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Machine learning algorithm facilitates fast derivation of light-scattering properties of sea salt aerosol - Quan Lin; Bingqi Yi; Lei Bi; Zhiyong Yang (Journal of Aerosol Science, 2025)

Hydro-mechanical interactions in CO2 storage: Critical parameters influencing coal mine at Shenhua's CCS site - Keyao Lin; Ning Wei; Yao Zhang; Shengnan Liu; Muhammad Ali; Wendong Wang; Quan Chen; Yongsheng Wang (Engineering Geology, 2025)

A novel catalytic ozonation mechanism of MIL-53(Fe70Ce30): Role of abundant oxygen vacancies and unsaturated metal centers generated via Ce-doping - Hui Yu; Xiaochuan Lin; Shuxin Ren; Kaiyang Chen; Quan Sun; Min Song; Chaoqun Tan (Chemical Engineering Journal, 2025)

Differential analysis and unified predictive modeling of capillary rise in sodium chloride and sodium sulfate saline soils - Yupeng Shen; Lin Wang; Quan Cao; Jamlick Kariuki; Chengcheng Luo (Arabian Journal of Geosciences, 2025)

Biocontrol potential of four Pseudomonas strains against tobacco black shank disease - Mingya Zhang; Quan Ren; Xiuqing Wu; Meng Liu; Lin Zhang; Qiong Yuan; Ning Lu; Yi Cao (Antonie van Leeuwenhoek, 2025)

Enhancing antibiotic removal in constructed wetlands: A MgFe-LDHs-based strategy for optimizing microbial communities and metabolic functions - Yu-Quan Zhong; Xiang-Long He; Yi-Hao Li; Hui Zhu; Jing-Wen Li; Hao Xu; Can Liu; Liang-Cheng Lin; Jun-Feng Wang (Journal of Hazardous Materials, 2025)

Collagenases from hepatopancreas and muscle of Litopenaeus vannamei: Purification, characterization and comparison of their behaviors in collagen degradation - Xu-Chen Xiao; Jia-Yin Huang; Yu-Lei Chen; Kai-Yuan Cao; Ru-Qing Yang; Duan-Quan Lin; Shu-Jun Hong; Yu-Ting Yang; Min-Jie Cao (Food Chemistry, 2025)

Monitoring of genetically modified crops in food products in Singapore - Yanwen Wang; Kung Ju Lin; Emily Huey Shyan Teo; Yong Quan Tan; Yuansheng Wu; Kern Rei Chng; Joanne Sheot Harn Chan; Li Kiang Tan (Food Control, 2025)

Special functionalized binder chemistry boosting high-rate and long-life sodium ion batteries - Jing-Chao Liu; Xiao Liu; Tao You; Yi-Fan Zhao; Feng-Quan Liu; Chen Wang; Lin Li (Chemical Engineering Journal, 2025)

Energy consumption and environmental impact analysis of biomass graded deconstruction activation catalytic deoxygenation for rich single-ring aromatic bio-oil preparation - Fengchao Wang; Bin Xu; Lin Lang; Cui Quan; Huacai Liu; Weizhen Li; Wenshen Yang; Ningbo Gao; Xiuli Yin (Bioresource Technology, 2025)

The potential of golden apple snail (Pomacea canaliculata) meat meal as an alternative protein source for juvenile Chinese mitten crab (Eriocheir sinensis) - Wenxiang Yao; Chunyan Zhang; Rui Jia; Sitong Zhao; Weibo Jiang; Guoan Hua; Sizhe Zhao; Apeng Lin; Jianguo Wang; Quan Wang (Frontiers in Marine Science, 2025)
This study investigated the effects of replacing dietary fish meal (FM) with golden apple snail ( Pomacea canaliculata ) meat meal (PCM) on growth performance, non-specific immunity and intestinal health of juvenile Chinese mitten crab ( Eriocheir sinensis ). Four hundred juvenile Chinese mitten crabs (2.39 ± 0.03) g were randomly distributed into five groups in quadruplicate (20 crabs per tank), and each group was fed with diets that replaced FM with PCM at 0% (FM-20, containing 200 g/kg FM), 25% (FM-15), 50% (FM-10), 75% (FM-5), and 100% (FM-0) for 8 weeks, respectively. The results showed that the growth, whole body composition, digestive enzyme activities, antioxidant performance, non-specific immunity, intestinal histology and microbiota composition of FM-15 and FM-10 groups all reached the same level as the FM-20 group ( P > 0.05). While the replacement ratio reached 75%, the FCR was significantly increased and the peritrophic membrane thickness was significantly decreased ( P< 0.05). When 100% FM was replaced, significantly decreased the growth performance, serum antioxidant and immune enzyme activities, mid-intestine folds height, width and the peritrophic membrane thickness ( P< 0.05), and significantly increased the abundance of intestinal harmful bacteria Vibrio ( P< 0.05). In conclusion, PCM can effectively replace 50% dietary FM (100 g/kg) without negative effects on the growth performance, intestinal health, serum immune, and antioxidant indexes of juvenile E. sinensis .

Approximate the optimal energy management strategy for plug-in hybrid electric vehicle from the constant-sum game - Jincheng Hu; Yang Lin; He Tong; Quan Zhou; Zheng Chen; Yonggang Liu; Jingjing Jiang; Yuanjian Zhang (Journal of Cleaner Production, 2025)

Integrative analyzing the molecular basis of Clerodendranthus spicatus aqueous extract in hyperuricemia nephropathy via network pharmacology and experimental validation - Chuang Li; Danyao Lin; Jianting Ouyang; Junyi Liu; Shouhai Wu; Delun Li; Fan Yang; Haohao Quan; Yimeng Li; Qiaoru Wu; Guirui Huang; Wei Mao (Food Bioscience, 2025)

Biochar doping of synthesized mordenite improves adsorption and oxidation in As(III) removal: Experiments and DFT calculations - Guangwei Wu; Jing Lin; Bin Wang; Fuyang Huang; Quan Long; Weiguo Tu (Environmental Research, 2025)

2-Mercapto-1,3,4-thiadiazole-functionalized gold nanoclusters as a comparable bactericidal nanoantibiotic to vancomycin in treating methicillin-resistant Staphylococcus aureus infections - Quan-Quan Zhuang; Jia-Xin Ma; Yi-Ming Zheng; Lin-Yan Lu; Jia-Lin Yang; Qing-Qing Chen; Xiao-Li Yan; Yan-Cheng Jiang; Hao-Hua Deng; Wei Chen; Gang Liu (Chemical Engineering Journal, 2025)

Perylene diimide cathode interface layer with siloxane bay-modification for efficient and stable organic solar cells - Dan Zhou; Yujie Pu; Yanyan Wang; Lin Hu; Jianwei Quan; Senmei Lan; Jiangang Ma; Fang Wang; Wentian Wan; Yongfen Tong; Ruizhi Lv; Haitao Xu; et al. (Chemical Engineering Journal, 2025)

Indian ocean-type mantle domain in the Carboniferous Qushiman ophiolite in the Northern Pamir: Significance for the intra-oceanic subduction in the Paleo-Tethys Ocean - Yan Jing; Chuan-Lin Zhang; Chen Wang; Masumeh Sargazi; Zhi-Hao Song; Yi-kang Quan; Zhi-Kai Xu; Xiao-Qiang Liu; Hong-Ran Wang (Chemical Geology, 2025)

Late Mesozoic Wangxiang Composite Granitic Pluton, South China Block: Implications to Magma Emplacement and Evolution from Geochemical Proxies - Quan Ou; Jing-Yi Liu; Feng Zi; Bruna B. Carvalho; Xiaoping Long; Jian-Qing Lai; Kun Wang; Zi-Qi Jiang; Yi-Zhi Liu; Zheng-Lin Li; Hong-Yun Wang (Journal of Earth Science, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Investigation of seasonal variations in submarine groundwater discharge using radium isotopes under drought conditions in northwestern coastal Taiwan - Minh-Quan Dang; Feng-Hsin Hsu; Chih-Chieh Su; Shih-Jung Wang; Ching-Chou Fu; In-Tian Lin (Journal of Hydrology, 2025)

Microbial augmented aerobic composting for effective phthalates degradation in activated sludge - Bogui Pan; Hong Tian; Qi-Feng Liang; Hong-Jia Huang; Yi-Tong Huang; Bai-Lin Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Management, 2025)

Human milk oligosaccharides ameliorate intestinal barrier in aging honey bee by regulating gut microbiota - Xiaoya Lin; Yingying Lin; Yueyi Wang; Yujie Meng; Yafei Zhang; Heng Quan; Yao Lu; Hao Zheng; Huiyuan Guo (Food Bioscience, 2025)

Concurrent optimization of truss structures and build directions for multi-axis additive manufacturing - Jun Ye; Xiaoyang Lin; Hongjia Lu; Linwei He; Guan Quan; Cheng Huang; Paul Shepherd (Engineering Structures, 2025)

Source specific fine particles and rates of asthma and COPD healthcare encounters pre- and post-implementation of the Tier 3 vehicle emissions control regulations - Shao Lin; Yukang Xue; Sathvik Thandra; Quan Qi; Sally W. Thurston; Daniel P. Croft; Mark J. Utell; Philip K. Hopke; David Q. Rich (Journal of Hazardous Materials, 2025)

Contribution of phosphorylation modification by sodium tripolyphosphate to the functional properties of hollow zein nanoparticles - Sheng-qi Rao; Cao-chen Jia; Lin Du; Wei-biao Zhou; Wen-xuan Hu; Yi Jiang; Zhi-rong Wang; Zhen-quan Yang (Food Research International, 2025)

High toughness and programmable strength in ion gels via hydrogen bond-induced microphase separation - Qi Wang; Liangke Lin; Tao Zhang; Zhe Wang; Xiaohan Liu; Qi Quan; Guohang Zhang; Yuanjie Zhou; Jiangwei Li; Xiaoyan Zhou; Minzhi Chen (Chemical Engineering Journal, 2025)

Impact of DNA Extraction Methods on Gut Microbiome Profiles: A Comparative Metagenomic Study - Yanni Pu; Xiaofeng Zhou; Hao Cai; Tao Lou; Chenglin Liu; Mengmeng Kong; Zhonghan Sun; Yanren Wang; Ruyi Zhang; Yuxuan Zhu; Lin Ye; Yuanting Zheng; et al. (Phenomics, 2025)

N6-methyladenosine RNA methylation regulates microplastics-induced cell senescence in the rainbow trout liver - Fang Ma; Zhe Liu; Jinqiang Quan; Yijun Yuan; Jianzhou Wang; Xiangjun Zhou; Jing Wang; Lei Shen; Dunting Tie; Minlan Yang; Yang Lin; Guoyu Song; et al. (Science of The Total Environment, 2025)

Spatiotemporal characteristics and forcing mechanism of precipitation changes in the Nanling Mountains and surrounding regions in South China over the past 60 years - Durui Lin; Wei Zhong; Xiaojun Wang; Mingying Quan; Tianhang Li; Enlou Zhang (Theoretical and Applied Climatology, 2025)

Blocking the PD-1 signal transduction by occupying the phosphorylated ITSM recognition site of SHP-2 - Wenjie Li; Wenyi Mei; Hewei Jiang; Jie Wang; Xiaoli Li; Lina Quan; Yanyan Diao; Yanni Ma; Sisi Fan; Zhuwei Xie; Mengdie Gong; Huan Zhu; et al. (Science China Life Sciences, 2025)

Correction to: Potential effects of inulin as a dietary supplement on immunity, antioxidant, and intestinal health of spotted sea bass (Lateolabrax maculatus) fed a high‑fat diet - Fuqiang Quan; Xiujuan Wang; Luimin Kong; Yi Lin; Hao Lin; Sishun Zhou; Jianrong Ma; Yanbo Zhao; Yunting Zhao; Longhui Liu; ZhongBao Li (Aquaculture International, 2025)

Effects of curcumin supplementation in high-fat diet on intestinal health of spotted sea bass (Lateolabrax maculatus) - Xiujuan Wang; Fuqiang Quan; Zhangfan Huang; Luming Kong; Yi Lin; Hao Lin; Sishun Zhou; Jianrong Ma; Yanbo Zhao; Yunting Zhao; Longhui Liu; Zhongbao Li (Aquaculture International, 2025)

Potential effects of inulin as a dietary supplement on immunity, antioxidant, and intestinal health of spotted sea bass (Lateolabrax maculatus) fed a high-fat diet - Fuqiang Quan; Xiujuan Wang; Luimin Kong; Yi Lin; Hao Lin; Sishun Zhou; Jianrong Ma; Yanbo Zhao; Yunting Zhao; Longhui Liu; ZhongBao Li (Aquaculture International, 2025)

Unraveling the role of freight facility development in the dynamics of gentrification - Zhengtao Qin; Chengcheng Yu; Haocheng Lin; Chao Yang; Quan Yuan (Transportation Research Part D: Transport and Environment, 2024)

Eicosatrienoic acid enhances the quality of in vitro matured porcine oocytes by reducing PRKN-mediated ubiquitination of CISD2 - Zhi-Yong An; Sheng-Zhong Han; Zhou-Yan Li; Shuang-Yan Chang; Xiu-Li Zhang; Gao-Jie Lu; Tuo Zhang; Biao-Hu Quan; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Environmental DNA reveals the spatiotemporal distribution and migration characteristics of the Yangtze finless porpoise, the sole aquatic mammal in the Yangtze River - Qiao Qiao; Quan Zhou; Jie Wang; Hao-jie Lin; Bo-yang Li; Hao Du; Zhen-guang Yan (Environmental Research, 2024)

Alpha-ketoglutarate supramolecular network accelerates diabetic wound healing through exudates management and neovascularization - Yimeng Cai; Pochun Lin; Yuhan Li; Linfeng Liu; Shuqin Cao; Bin Zhao; Yueying Wang; Wei Song; Qian Wang; Xinyan Gan; Ke Xu; Qingheng Wu; et al. (Chemical Engineering Journal, 2024)

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

Early Cretaceous mafic dikes in the eastern North China Craton: implications for the effect of slab subduction on the mantle sources - Chao Li; Lin Li; Ju-Quan Zhang; M. Santosh; Sheng-Rong Li; Bowen Wei; Cong Li (International Geology Review, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Parkin deficiency exacerbates particulate matter-induced injury by enhancing airway epithelial necroptosis - Yuting Lin; Meiyu Quan; Xibin Wang; Wanqi Miao; Haibo Xu; Baiqi He; Bin Liu; Yanxia Zhang; Yijing Chen; Binqian Zhou; Mengying Xu; Li Dong; et al. (Science of The Total Environment, 2024)

Synergistic management of nitrogen contamination in overflow wastewater and algal proliferation in lake receiving wastewater based on electrochemical oxidation process - Ya-Ning Wang; Ding Li; Lin Liu; Jia-Fang Xie; Zhi-Tang Lyu; Quan-Bao Zhao; Yu-Ming Zheng (Process Safety and Environmental Protection, 2024)

Extraction, phytochemicals characterization, in vivo and in vitro anti-diabetic ability of non-extractable polyphenols from Undaria pinnatifida - Chun-yan Peng; Quan-yuan Xie; Xing Xie; Lin-yi Tang; Tian-xin Ma; Dai-wei Ke; Zong-cai Tu; Lu Zhang (Food Research International, 2024)

PM2.5 and its components and respiratory disease healthcare encounters – Unanticipated increased exposure-response relationships in recent years after environmental policies - Shao Lin; Yukang Xue; Sathvik Thandra; Quan Qi; Philip K. Hopke; Sally W. Thurston; Daniel P. Croft; Mark J. Utell; David Q. Rich (Environmental Pollution, 2024)

Iron driven organic carbon capture, pretreatment, recovery and upgrade in wastewater: Process technologies, mechanisms, and implications - Quan Liao; Lianpeng Sun; Hui Lu; Xianglin Qin; Junhong Liu; Xinzhe Zhu; Xiao-yan Li; Lin Lin; Ruo-hong Li (Water Research, 2024)

The thermal degradation of glucomoringin and changes of phenolic compounds in moringa seed kernels during different degrees of roasting - Yunjiao Liu; Fion Wei Lin Chin; Dejian Huang; Shao-Quan Liu; Yuyun Lu (Food Chemistry, 2024)

Properties of coaxial polycaprolactone cinnamaldehyde chitosan nanoparticles electrospun membrane and its effect on the shelf life of meat - Jiaman Xu; Yan Gao; Weichao Chen; Maokun Sheng; Quan Lin; Hui Shi; Yulong Tan (Food Control, 2024)

Complex variable solution on over-/under-break shallow tunnelling in gravitational geomaterial with reasonable far-field displacement - Luo-bin Lin; Fu-quan Chen; Jin-ping Zhuang (Computers and Geotechnics, 2024)

Defect engineering of sulfur vacancies in vanadium disulfide integrated with graphene as advanced potassium-ion battery cathode - Haoxiang Lin; Zhenxiang Wang; Jinghua Quan; Hongyan Li (Chemical Engineering Journal, 2024)

Adsorption of Pb(II) from aqueous environment on artificially synthesized mordenite and its biochar composite - Fuyang Huang; Jing Lin; Bin Wang; Quan Long; Weiguo Tu (Chemical Engineering Journal, 2024)

MCT1-mediated transport of valeric acid promotes porcine preimplantation embryo development by improving mitochondrial function and inhibiting the autophagic AMPK-ULK1 pathway - Xiu-Li Zhang; Zhi-Yong An; Gao-Jie Lu; Tuo Zhang; Cheng-Wei Liu; Meng-Qi Liu; Qing-Xin Wei; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Interpenetrating LiB/Li3BN2 phases enabling stable composite lithium metal anode - Piao Qing; Shaozhen Huang; Tuoya Naren; Quan Li; Haifeng Huang; Kecheng Long; Zhijian Liu; Lin Mei; Fu Sun; Weifeng Wei; Yu Zhang; Jianmin Ma; et al. (Science Bulletin, 2024)

Paospora carinifang n. gen., n. sp. (Microsporidia: Spragueidae), a parasite of the ridgetail white prawn, Palaemon carinicauda - Yuan Wang; Ying Na; Yan-qing Huang; Jun-fang Zhou; Shou-hu Li; Quan-lin Liu; Le-tian Li; Yuan-ge Chen; Wei Tian; Hai Chi; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2024)

Mining flotation reagents: Quantitative and robust analysis of metal-xanthate complexes in water - Wen-Jun Wu; Qing-Jun Zheng; Jing-Wen Liang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Nai-Xian Feng; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

A sustainable rapeseed oil-based bio-additive designed for hard asphalt binders: Performance, environmental, and economic assessment - Xiujie Quan; Zhixin Lin; Conglin Chen; Tao Ma; Yang Zhang (Fuel, 2024)

Small molecule perylene diimide derivatives with different bay site modifications as cathode interface layers for organic solar cells - Yanyan Wang; Dan Zhou; Senmei Lan; Jianwei Quan; Fang Wang; Lin Hu; Ruizhi Lv; Yujie Pu; Haitao Xu; Yongfen Tong; Bin Hu; Zhentian Xu; et al. (Chemical Engineering Journal, 2024)

Interlayer cross-linked MXene enables ultra-stable printed paper-based flexible sensor for real-time humidity monitoring - Hao-wen Zhang; Xiang Xu; Meng-lin Huang; Yang-sheng Wang; Zhao-quan Xu; Zhe-sheng Feng; Yagang Zhang; Yan Wang (Chemical Engineering Journal, 2024)

Win-win integration: A mitochondria targeted AIE photosensitizer for hypochlorite detection and type I & type II photodynamic therapy - Jiahao Ni; Lichao Yu; Yixuan Wang; Tong Yang; Yueqi Bai; Bowen Zheng; Manshan Liang; Xiaoxia Ye; Yun-Yun Quan; Feifei Lin; Zu-Sheng Huang (Analytica Chimica Acta, 2024)

A comprehensive review of matcha: production, food application, potential health benefits, and gastrointestinal fate of main phenolics - Jian-Hui Ye; Qi-Ting Fang; Lin Zeng; Ru-Yi Liu; Lu Lu; Jun-Jie Dong; Jun-Feng Yin; Yue-Rong Liang; Yong-Quan Xu; Zhong-Hua Liu (Critical Reviews in Food Science and Nutrition, 2024)

Creating most needed customized bus services: A collaborative analysis of user-route dynamics - Chengcheng Yu; Haocheng Lin; Yitong Chen; Chao Yang; Ailing Yin; Quan Yuan (Transportation Research Part D: Transport and Environment, 2024)

The role of Pleistocene dispersal in shaping species richness of sky island wintergreens from the Himalaya-Hengduan Mountains - Xiao-Juan Cheng; Peter W. Fritsch; Yan-Jun Lin; Guo-Hong Li; Yan-Quan Chen; Ming-Ying Zhang; Lu Lu (Molecular Phylogenetics and Evolution, 2024)

Dynamic changes of key metabolites in Longjing green tea during processing revealed by widely targeted metabolomic profiling and sensory experiments - Lin Zeng; Yan-Qing Fu; Ying Gao; Fang Wang; Shuang Liang; Jun-Feng Yin; Marie-Laure Fauconnier; Lijing Ke; Yong-Quan Xu (Food Chemistry, 2024)

Effects of biotransformed okara as a meat extender on the physicochemical properties and baking characteristics of pork jerkies - Lin Ya Eunis Keong; Mingzhan Toh; Yuyun Lu; Shao-Quan Liu (Food Bioscience, 2024)

Solar-driven adaptive radiative cooling coating with polymer carbon dots-enhanced photoluminescence for urban skin - Quan Gong; Ho Chun Wong; Jianheng Chen; Pei Li; Lin Lu (Chemical Engineering Journal, 2024)

Injectable photocrosslinkable acellular cartilage matrix hydrogel loaded with exosomes for promoting growth plate injury repair - Xinxin Si; Quan Zhang; Bo Ning; Lei Qiang; Qiang Li; Yihao Liu; Minjie Fan; Jing Shan; Guanlu Shen; Zichen Lin; Pengfei Zheng (Chemical Engineering Journal, 2024)

A quantitative optimization method for rockfall passive nets on high-steep slopes: case study of the Feishuiyan slope - Yu-chen Li; Nan Jiang; Jun-lin Chen; Shi-quan Chen; Yu-chuan Yang; Jia-wen Zhou (Landslides, 2024)

Prognostic model incorporating immune checkpoint genes to predict the immunotherapy efficacy for lung adenocarcinoma: a cohort study integrating machine learning algorithms - Xi-Lin Yang; Zheng Zeng; Chen Wang; Guang-Yu Wang; Fu-Quan Zhang (Immunologic Research, 2024)

A simple numerical simulation model can elucidate the key factors for designing a miniaturized ion trap mass spectrometer - Xinming Huo; Lin Gan; Xinyue Ding; Quan Yu; Bin Zhou; Jianhua Zhou; Xiang Qian (Analytica Chimica Acta, 2024)

Can habitual tea drinking be an effective approach against age-related neurodegenerative cognitive disorders: A systematic review and meta-analysis of epidemiological evidence - Wei Quan; Yong Lin; Huiyu Zou; Maiquan Li; Jie Luo; Zhiyong He; Jie Chen; Zhonghua Liu (Critical Reviews in Food Science and Nutrition, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Integrated strategies for road transportation-related multi-pollutant control: A cross-departmental policy mix - Chengcheng Yu; Zhengtao Qin; Yougeng Lu; Haocheng Lin; Chao Yang; Quan Yuan; Qingyang Wu (Transportation Research Part D: Transport and Environment, 2024)

Release of lead, copper, zinc from the initial corrosion of brass water meter in drinking water: Influences of solution composition and electrochemical characterization - Ching-Hsuan Hsu; Ding-Quan Ng; Yi-Pin Lin (Environmental Pollution, 2024)

An improved representative of stomatal models for predicting diurnal stomatal conductance at low irradiance and vapor pressure deficit in tropical rainforest trees - Wei Xue; Xue-min He; Quan Wang; Pei-jun Shi; Guang-hui Lv; Jian-feng Huang; Da Yang; Jiao-lin Zhang (Agricultural and Forest Meteorology, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Hidden danger: The long-term effect of ultrafine particles on mortality and its sociodemographic disparities in New York State - Quan Qi; Fangqun Yu; Arshad A. Nair; Sam S.S. Lau; Gan Luo; Imran Mithu; Wangjian Zhang; Sean Li; Shao Lin (Journal of Hazardous Materials, 2024)

In-depth impact evaluation of binders on the mechanical properties and CO2 capture performance of CaO-based particles - Xuehua Shen; Ruiheng Zhang; Yiping Su; Han Lin; Feng Xie; Yingying Cai; Guanghuan Li; Jiali Hua; Feng Yan; Zewei Quan; Zuotai Zhang (Journal of Environmental Chemical Engineering, 2024)

The impacts of different roasting degrees on aroma compounds profiles of moringa seed kernels and its oil - Yunjiao Liu; Fion Wei Lin Chin; Jingcan Sun; Shao-Quan Liu; Yuyun Lu (Food Bioscience, 2024)

Can drinking tea become an effective way to alleviate the extraintestinal manifestations of inflammatory bowel disease: A comprehensive review - Yong Lin; Siling Xie; Lizheng Xiao; Zhenyun Liu; Wanping Ke; Jian-an Huang; Zhonghua Liu; Wei Quan (Food Bioscience, 2024)

MetaIBM: A Python-based library for individual-based modelling of eco-evolutionary dynamics in spatial-explicit metacommunities - Jian-Hao Lin; Yu-Juan Quan; Bo-Ping Han (Ecological Modelling, 2024)

Study of a commercial-scale poultry manure oxy-fuel gasification plant via CFD modeling and safety assessment - Qinwen Liu; Yiying Wang; Wei Quan Leong; Yonghua Gu; Alexander Lin; Yuchen Wang; Aibing Yu; Wenqi Zhong; Chi-Hwa Wang (Biomass and Bioenergy, 2024)

Debris flow susceptibility assessment based on boosting ensemble learning techniques: a case study in the Tumen River basin, China - Zelu Chen; Hechun Quan; Ri Jin; Zhehao Lin; Guangzhu Jin (Stochastic Environmental Research and Risk Assessment, 2024)

Integrated analysis of miRNAs, transcriptome and phytohormones in the flowering time regulatory network of tea oil camellia - Haixiao Fan; Xiaoling Wang; Huiqi Zhong; Kehui Quan; Ruohan Yu; Shiying Ma; Siqiong Song; Mengfei Lin (Physiology and Molecular Biology of Plants, 2024)

Effects of Coal Thickness on the Fractal Dimension of Gas Migration Channels: Laboratory and Field Study of a Gassy Coal Mine - Risheng Zhuo; Pengxiang Zhao; Shugang Li; Haifei Lin; Hui Liu; Xiangguo Kong; Shikui Jin; Zhen Wang; Quan Jin (Natural Resources Research, 2024)

A novel strategy for enhancing the stability of aptamer conformations in heavy metal ion detection - Shi Quan Qian; Min Yuan; Xian Wei Zuo; Hui Cao; Jin Song Yu; Li-Ling Hao; Kun Lin Yang; Fei Xu (Analytica Chimica Acta, 2024)

Biodegradation of phthalate acid esters and whole-genome analysis of a novel Streptomyces sp. FZ201 isolated from natural habitats - Nai-Xian Feng; Da-Wei Li; Fei Zhang; Hui Bin; Yi-Tong Huang; Lei Xiang; Bai-Lin Liu; Quan-Ying Cai; Yan-Wen Li; De-Lin Xu; Yunchang Xie; Ce-Hui Mo (Journal of Hazardous Materials, 2024)

Overall quality changes and deterioration mechanism of fragrant rapeseed oils during 6-Month storage - Chen Chen; Ping-Ping Ye; Feng-Jie Cui; Ming Tan; Hai-Bo Zhang; Tong-Lin Zhou; Jian-Cheng Shi; Xue-Quan Shu; Zhi-Wei Chen (Food Chemistry, 2024)

Establishment of a cobia (Rachycentron canadum) gill cell line: A valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2024)

Role of sea salt in modulating biomass-to-biocrude conversion via hydrothermal liquefaction - Xiaoyu Lin; Wangfang Ye; Yifan Mao; Zhiyu Li; Qian Lan; Quan He; Kang Kang; Liang Zhang; Tao Shui; Yulong Wu; Xiaomei Zhong; Jie Yang (Desalination, 2024)

Glucose-Responsive hydrogel optimizing Fenton reaction to eradicate multidrug-resistant bacteria for infected diabetic wound healing - Xingchen Li; Zifan Meng; Lin Guan; Annan Liu; Lei Li; Maja D. Nešić; Bai Yang; Wenrui Qu; Quan Lin (Chemical Engineering Journal, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

Causal role of myeloid cells in Parkinson’s disease: Mendelian randomization study - Wei Quan; Yidan Qin; Jia Li; Lin Wang; Jia Song; Jing Xu; Jiajun Chen (Inflammation Research, 2024)

Predictive Model to Identify the Long Time Survivor in Patients with Glioblastoma: A Cohort Study Integrating Machine Learning Algorithms - Xi-Lin Yang; Zheng Zeng; Chen Wang; Yun-Long Sheng; Guang-Yu Wang; Fu-Quan Zhang; Xin Lian (Journal of Molecular Neuroscience, 2024)

Heavy metal migration dynamics and solid-liquid distribution strategy in abandoned tailing soils - Bohan Wu; Quan Wan; Xiao Li; Shukun Lin; Yanqi Jiang; Xu Yang; Jingjing Li; Qingqi Lin; Jean Louis Morel; Rongliang Qiu (Journal of Hazardous Materials, 2024)

Controllable lignin valorization to value-added aromatic chemicals by a UV-assisted ternary heterogeneous photo-fenton catalytic system - Fen Wang; Lin Zhang; Zhiping Wu; Wenbo Peng; Peng Zhan; Lishu Shao; Hui Wang; Yan Qing; Hanxue Lin; Quan Wei; Na Liu; Zhaohui Tong (Fuel, 2024)

MnO2 nanozyme with lanthanide-based radiosensitization for advanced radiotherapy by tumor microenvironment triggering STING pathway activation - Meiling Tan; Zhimin Gao; Xiaozhao Wang; Chen Lin; Yuchi Wan; Wenyu Xie; Wei Chen; Yaru Zhang; Zewei Quan; Zhiyao Hou (Chemical Engineering Journal, 2024)

Non-contact humidity monitoring: Boosting the performance of all-printed humidity sensor using PDDA-modified Ti3C2Tx nanoribbons - Meng-lin Huang; Jie Lu; Jing-xin Ji; Hao-wen Zhang; Zhao-quan Xu; Zhe-sheng Feng; Wei Wu; Yan Wang (Chemical Engineering Journal, 2024)

Effects of forest thinning on soil microbial biomass and enzyme activity - Hongwei Xu; Quan Gan; Lulu Huang; Xingyu Pan; Tongwei Liu; Ruiyang Wang; Limengjie Wang; Li Zhang; Han Li; Lixia Wang; Sining Liu; Jiao Li; et al. (CATENA, 2024)

Protein extraction from chlorella pyrenoidosa microalgae: Green methodologies, functional assessment, and waste stream valorization for bioenergy production - Zijing Wang; Wangfang Ye; Yijing Wu; Xiaoyu Lin; Cuirong Luan; Xiaowei Xie; Yue Peng; Xiaohong Sun; Chuangyang Shi; Yuancai Lv; Jianlin Shen; Tess Astatkie; et al. (Bioresource Technology, 2024)

Infant Exposure and Risk Assessment of Organophosphorus Flame Retardants in Human Breast Milk from The Southeast City, China - Quan Zhang; Yan Wang; Jianlin Lou; Zeteng Ying; Xunjie Mo; Shu Lin (Exposure and Health, 2024)

Biochemical and Transcriptome Analysis Reveals Pigment Biosynthesis Influenced Chlorina Leaf Formation in Anoectochilus roxburghii (Wall.) Lindl - Xiu-Xian Ye; Yi-Quan Chen; Jian-She Wu; Huai-Qin Zhong; Bing Lin; Min-Ling Huang; Rong-Hui Fan (Biochemical Genetics, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Establishment of a TaqMan probe‐based qPCR assay for detecting microsporidia Enterospora epinepheli in grouper - Quan‐lin Liu; Yuan Wang; Jie Chen; Guo‐qing Pan; Yan‐Feng Yue; Ze‐Yang Zhou; Wen‐hong Fang (Journal of Fish Diseases, 2024)
Enterospora epinepheli is an intranuclear microsporidian parasite causing serious emaciative disease in hatchery‐bred juvenile groupers ( Epinephelus spp.). Rapid and sensitive detection is urgently needed as its chronic infection tends to cause emaciation as well as white faeces syndrome and results in fry mortality. This study established a TaqMan probe‐based real‐time quantitative PCR assays targeting the small subunit rRNA (SSU) gene of E. epinepheli. The relationship between the standard curve of cycle threshold (Ct) and the logarithmic starting quantity (SQ) was determined as Ct = −3.177 lg (SQ) + 38.397. The correlation coefficient ( R 2 ) was 0.999, and the amplification efficiency was 106.4%. The detection limit of the TaqMan probe‐based qPCR assay was 1.0 × 10 1 copies/μL and that is 100 times sensitive than the traditional PCR method. There is no cross‐reaction with other aquatic microsporidia such as Ecytonucleospora hepatopenaei , Nucleospora hippocampi , Potaspora sp., Ameson portunus. The intra‐assay and inter‐assay showed great repeatability and reproducibility. In addition, the test of clinical samples showed that this assay effectively detected E. epinepheli in the grouper's intestine tissue. The established TaqMan qPCR assays will be a valuable diagnostic tool for the epidemiological investigation as well as prevention and control of E. epinepheli .

Cancer screening in hospitalized ischemic stroke patients: a multicenter study focused on multiparametric analysis to improve management of occult cancers - Jie Fang; Jielong Wu; Ganji Hong; Liangcheng Zheng; Lu Yu; Xiuping Liu; Pan Lin; Zhenzhen Yu; Dan Chen; Qing Lin; Chuya Jing; Qiuhong Zhang; et al. (EPMA Journal, 2024)

Adaptive shifts in plant traits associated with nitrogen removal driven by phytoremediation strategies in subtropical river restoration - Yu Xin; Lin Liu; Xiao-Ru Yang; Le-Yang Yang; Shan-Bin Guang; Yu-Ming Zheng; Quan-Bao Zhao (Water Research, 2024)

Asynchronous variations of mercury accumulation since the last deglaciation in the eastern and western Nanling mountains in South China - Xiaojun Wang; Wei Zhong; Mingying Quan; Tianhang Li; Durui Lin; Chunxia Zhang (Quaternary Science Reviews, 2024)

Unraveling the effects of sodium carbonate on hydrothermal liquefaction through individual biomass model component and machine learning-enabled prediction - Wangfang Ye; Xiaoyu Lin; Xiaomei Zhong; Qian Lan; Guifang Yang; Jianhui Huang; Yijing Wu; Zeyuan Zhao; Quan (Sophia) He; Yulong Wu; Xin Xu; Jie Yang (Fuel, 2024)

Association of urinary polycyclic aromatic hydrocarbon metabolites with gestational diabetes mellitus and gestational hypertension among pregnant women in Southwest China: A cross-sectional study - Dengqing Liao; Shimin Xiong; Songlin An; Lin Tao; Lulu Dai; Yingkuan Tian; Wei Chen; Caidie He; Pei Xu; Nian Wu; Xiang Liu; Haonan Zhang; et al. (Environmental Pollution, 2024)

Inhibition mechanisms of biochar-derived dissolved organic matter to triclosan photodegradation: A remarkable role of aliphatics - Lin Wang; Jing Feng; Quan Chen; Hao Jiang; Jing Zhao; Zhaofeng Chang; Xinhua He; Fangfang Li; Bo Pan (Environmental Pollution, 2024)

A new complex variable solution on noncircular shallow tunnelling with reasonable far-field displacement - Luo-bin Lin; Fu-quan Chen; Shang-shun Lin (Computers and Geotechnics, 2024)

β-Lapachone induces ferroptosis of colorectal cancer cells via NCOA4-mediated ferritinophagy by activating JNK pathway - Lei Zhao; Hui Miao; Mingqi Quan; Shuhao Wang; Yu Zhang; Houkun Zhou; Xianglan Zhang; Zhenhua Lin; Junjie Piao (Chemico-Biological Interactions, 2024)

Green Synthesis of Carbon Aerogel Derived from Lotus Root for the Removal of Ciprofloxacin, Oil, Organic Solvents, and Supercapacitor Applications - Mai Thanh Phong; Phan Minh Tu; Nguyen Duy Hai; Nguyen Thanh Hoai Nam; Vo Minh Quan; Tran Ngoc Son; Tong Hoang Lin; Le Gia Han; Nguyen Truong Son; Nguyen Huu Hieu; Ton That Buu (Water, Air, & Soil Pollution, 2024)

Targeting Ferroptosis Promotes Functional Recovery by Mitigating White Matter Injury Following Acute Carbon Monoxide Poisoning - Shuhong Wang; Binyuan Xiong; Yin Tian; Quan Hu; Xuheng Jiang; Ji Zhang; Lin Chen; Ruilie Wang; Mo Li; Xin Zhou; Tianxi Zhang; Hongfei Ge; et al. (Molecular Neurobiology, 2024)

Exogenous stimulation-induced biosynthesis of volatile compounds: Aroma formation of oolong tea at postharvest stage - Lin Zeng; Shan Jin; Yan-Qun Xu; Daniel Granato; Yan-Qing Fu; Wei-Jiang Sun; Jun-Feng Yin; Yong-Quan Xu (Critical Reviews in Food Science and Nutrition, 2024)

Changes in properties of human milk under different conditions of frozen storage - Kaibo Wang; Yanfeng Zhao; Sijia Song; Yingying Lin; Yujia Luo; Yafei Zhang; Yi Xue; Wusun Li; Yuning Zhang; Yao Lu; Heng Quan; Hao Zhang; et al. (Food Research International, 2024)

Bacterial, short-chain fatty acid and gas profiles of partially hydrolyzed guar gum in vitro fermentation by human fecal microbiota - Xiong-E Pi; Hao Fu; Xiao-Xia Yang; Zai-Chun Yu; Wei-Lin Teng; Yinjun Zhang; Xue-Wei Ye; Hui Hui Quan; Li-Zhi Lu; Wei Liu (Food Chemistry, 2024)

pH-tailored activated water reservoir for rapid solar water purification via dual-layer hydrogel architecture - Xue-Tong Yang; Huan Lin; Jia-Chen Zhang; Gangqiang Yu; Yuelian Peng; Quan-Fu An (Chemical Engineering Journal, 2024)

Biodegradation of polystyrene microplastics by superworms (larve of Zophobas atratus): Gut microbiota transition, and putative metabolic ways - Zhaolin Quan; Zixi Zhao; Zhimin Liu; Weijun Wang; Shunyu Yao; Huiren Liu; Xiaoqiu Lin; Qing X. Li; Hai Yan; Xiaolu Liu (Chemosphere, 2023)

Single-cell RNA sequencing reveals a hierarchical transcriptional regulatory network of terpenoid biosynthesis in cotton secretory glandular cells - Jia-Ling Lin; Longxian Chen; Wen-Kai Wu; Xiao-Xiang Guo; Cheng-Hui Yu; Min Xu; Gui-Bin Nie; Jun-ling Dun; Yan Li; Baofu Xu; Ling-Jian Wang; Xiao-Ya Chen; et al. (Molecular Plant, 2023)

Model development of deep space-source heat pump system and its feasibility analysis - Linrui Jia; Lin Lu; Jianheng Chen; Quan Gong (Journal of Cleaner Production, 2023)

A simulated drier climate reduces growth and alters functional traits of Eucalyptus trees: A three-year experiment in South China - Ling Yang; Jiejun Kong; Yaqian Gao; Zetao Chen; Yubiao Lin; Shucai Zeng; Yan Su; Jiyue Li; Qian He; Quan Qiu (Forest Ecology and Management, 2023)

Non-targeted analysis and risk assessment of intentionally and non-intentionally added substances migrating from the emerging biodegradable food contact material poly(butylene adipate-co-terephthalate)/modified starch blend film - Jun Lin; Wei-Liang Wu; Ai-Hua Zhong; Yan-Ping Xian; Huai-Ning Zhong; Ben Dong; Ming Liang; Jun-Peng Hu; Yong-Ning Wu; Xing-Fen Yang; Hai-Xia Sui; Quan Zhou (Food Packaging and Shelf Life, 2023)

Environmental exposure disparities in ultrafine particles and PM2.5 by urbanicity and socio-demographics in New York state, 2013–2020 - Arshad Arjunan Nair; Shao Lin; Gan Luo; Ian Ryan; Quan Qi; Xinlei Deng; Fangqun Yu (Environmental Research, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Shoot Production of Solanum tuberosum L. ‘Yansi’ Using a Simple Continuous Immersion Airlift Bioreactor Culture System - Hang-Lin Song; Rong-de Jin; Xue-Li Quan; Ji-De Zhang; Wen-Wen Qi; Xi-Hua Cui (Potato Research, 2023)

Grazing practices affect phyllosphere and rhizosphere bacterial communities of Kobresia humilis by altering their network stability - Jin-Peng Hu; Ming-Xu Zhang; Zhao-Long Lü; Yuan-Yuan He; Xiao-Xia Yang; Aziz Khan; You-Cai Xiong; Xiang-Ling Fang; Quan-Min Dong; Jin-Lin Zhang (Science of The Total Environment, 2023)

The iLABdb: a web-based integrated lactic acid bacteria database - Hao Jin; Teng Ma; Lin Chen; Lai-Yu Kwok; Keyu Quan; Yalin Li; Zeng Zhang; Tong Chen; Jiachao Zhang; Zhihong Sun; Heping Zhang (Science Bulletin, 2023)

Advancing hydrochar production and application: A critical examination of microwave irradiation and blended feedstocks synergy - Shaorong Du; Quan Zhang; Wangfang Ye; Zijing Wang; Zilin Liu; Jianhui Huang; Xin Xu; Yijing Wu; Xiaoyu Lin; Quan Sophia He; Sonil Nanda; Rahil Changotra; et al. (Journal of Cleaner Production, 2023)

Environmentally-friendly, sustainable ScCO2-assisted fabrication of poly (lactic acid)/ramie fiber composite foams - Jiao Li; Yingxiao Wang; Jun Lin; Ya Liu; Guilong Wang; Dong Quan; Yanjin Guan; Guoqun Zhao; Shengcheng Ji (Journal of Cleaner Production, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Iron blocks autophagic flux and induces autophagosomes accumulation in microglia - Deqiang Fu; Xingyue Liang; Yuxuan Jiang; Jieping Liu; Xiaosi Lin; Quan Yang; Xue Chen; Ping Huang; Wei Wang; Wenlin Wu (Food and Chemical Toxicology, 2023)

Planktonic microbial community and biological metabolism in a subtropical drinking water river-reservoir system - Lin Liu; Yu Xin; Shan-Bin Guang; Guo-Fu Lin; Chao-Xiang Liu; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Research, 2023)

Antibiotic resistant genes profile in the surface water of subtropical drinking water river-reservoir system - Lin Liu; Shan-Bin Guang; Yu Xin; Jie Li; Guo-Fu Lin; Li-Qin Zeng; Shao-Qin He; Yu-Ming Zheng; Guan-Yu Chen; Quan-Bao Zhao (Environmental Pollution, 2023)

Reliability analysis of core power optimization control using Kalman filter for accelerator driven system based on reconfigurable computing - Jin-Yang Li; Huan Lin; Long Gu; You-Peng Zhang; Jun-Liang Du; Yong-Quan Wang; Cong Lin; Xing-Chen Zhou; Tian Wang (Annals of Nuclear Energy, 2023)

Sedimentary elements, evolutions and controlling factors of the Miocene channel system: a case study of the deep-water Taranaki Basin in New Zealand - Guangxu Wang; Wei Wu; Changsong Lin; Quan Li; Xiaoming Zhao; Yongsheng Zhou; Weiqing Liu; Shiqin Liang (Acta Oceanologica Sinica, 2023)

The shock of benzalkonium chloride on aerobic granular sludge system and its microbiological mechanism - Yuhao Tong; Peili Lu; Wenyu Zhang; Jun Liu; Yuhai Wang; Lin Quan; Aqiang Ding (Science of The Total Environment, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Recycling of subducted Indian continental crust constrained by late Cretaceous mafic dykes in Central Lhasa block of the Tibetan plateau - Lu-Lu Hao; Andrew C. Kerr; Qiang Wang; Lin Ma; Yue Qi; Ming Xiao; Quan Ou (Lithos, 2023)

Assessing the suitability of municipal sewage sludge and coconut bran as breeding medium for Oryza sativa L. seedlings and developing a standardized substrate - Linyi Lin; Jiemin Qin; Yu Zhang; Jiaxin Yin; Genmao Guo; Muhammad Amjad Khan; Yin Liu; Quan Liu; Qingqing Wang; Kenlin Chang; Ondřej Mašek; Junfeng Wang; et al. (Journal of Environmental Management, 2023)

Biotransformation of okara (soybean residue) through solid-state fermentation using probiotic Bacillus subtilis and Bacillus coagulans - Lin Ya Eunis Keong; Mingzhan Toh; Yuyun Lu; Shao-Quan Liu (Food Bioscience, 2023)

Prevalence, distribution, accumulation, and risk of environmental corticosteroids and estrogens in biofilms from the Pearl River Delta - Jian Gong; Ke-Xin Yang; Can-Yuan Lin; Qiang Li; Chong Han; Wei Tao; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; De-Xin Wang (Environmental Pollution, 2023)

A novel peridynamic solution for modelling saturated soil-pore fluid interaction in liquefaction analysis - Quan Gu; Zhe Lin; Lei Wang; Zhijian Qiu; Surong Huang; Shaofan Li (Computers and Geotechnics, 2023)

Twisting two-dimensional photothermal sponges for boosting solar steam generation - Feng Lu; Shao-Lin Wu; Lu-Na Quan; Zhi-Hui Zhong; Hao-Cheng Yang; Ming Xue (Chemical Engineering Journal, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

Genesis of No. 2 orebody of the Jinchuan magmatic Ni-Cu-(PGE) sulfide deposit, NW China: New constraints from the newly discovered deep extension - Ting-Mao Long; Xie-Yan Song; Jian Kang; Qing-Lin Liang; Yong-Cai Wang; De-Xian Li; Qi-Xing Ai; Wen-De Suo; Jian-Quan Lu (Mineralium Deposita, 2023)

A stabilized hybrid peridynamic method compatible with constitutive models of different dimensions - Quan Gu; Zhe Lin; Lei Wang; Surong Huang; Shaofan Li (Soil Dynamics and Earthquake Engineering, 2023)

Continuous extensional uplift controls the Silurian structural evolution of the Sichuan Basin, southwest China - Gen Li; Zhong-Quan Li; Dian Li; Heng-Lin Liu; Shan Yan; Gui-Ping Su; Xing-Wang Tian (Marine and Petroleum Geology, 2023)

Development of Au8 nanocluster-based fluorescent strip immunosensor for sensitive detection of aflatoxin B1 - Zi-Hui Shao; Aoqiang Zhai; Yue Hua; Hui-Lin Mo; Fuwei Xie; Xueli Zhao; Ge Zhao; Shuang-Quan Zang (Analytica Chimica Acta, 2023)

Analysis of Nord Stream explosions using seismic recordings - Yang Shen; Xiao-Lin Hu; Tong-Dong Wang; Wei Zhu; Quan-Shi Guo; Shuo Yang; Qiang Lu; De-Zhi Zhang; Wei-Guo Xiao (Applied Geophysics, 2023)

Nano-pesticide carrier O-Carboxymethyl chitosan is indigestible in Apis cerana cerana and affects intestinal flora - Sheng-nan Li; Hao Wu; Rui-quan Hou; Jing-tong Zhou; Su-kun Lin; Kun-yu Zhao; Rui-fei Wang; Su-qing Huang; Zhi-xiang Zhang (Science of The Total Environment, 2023)

Suspended particulate matter-associated environmental corticosteroids in the Pearl River, China: Occurrence, distribution, and partitioning - Jian Gong; Yong-Shun Zhou; Can-Yuan Lin; Qiang Li; Chong Han; Ke-Xin Yang; Ying Huang; Wei-Quan Lin; Cui-Qin Wu; Shu-Han Zhang; Jia-Yu Huang (Science of The Total Environment, 2023)

Multi-objective optimization of chemical process plant layout considering economy and inherent safety - Zi Lin; Lin-Quan Gong; Jing-Jing Xu; Jia-Jia Jiang; Jun-Cheng Jiang (Process Safety and Environmental Protection, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Where do we manage? Uncovering the hidden impact of human presence on mammal conservation in northern Myanmar - Ye Htet Lwin; Lin Wang; Guogang Li; Rui-Chang Quan (Biological Conservation, 2023)

Different grazers and grazing practices alter the growth, soil properties, and rhizosphere soil bacterial communities of Medicago ruthenica in the Qinghai-Tibetan Plateau grassland - Ming-Xu Zhang; Ling-Yu Zhao; Jin-Peng Hu; Aziz Khan; Xiao-Xia Yang; Quan-Min Dong; Christopher Rensing; Xiang-Ling Fang; Jin-Lin Zhang (Agriculture, Ecosystems & Environment, 2023)

Taxonomic and Morpho-Functional Photosynthetic Patterns of 18 Intertidal Macroalgal Species in the Guangdong–Hong Kong–Macao Greater Bay Area, China - Quan He; Linqing Liu; Yujie Qin; Qiang Lin; Guangyan Ni; Binbin Chen; Zengling Ma; Dinghui Zou; Gang Li (Journal of Marine Science and Engineering, 2023)
Macroalgae provide food for microbial, meio- and macro-faunal communities in coastal ecosystems, thus mediating nutrient dynamics and functions in these ecosystems. Because of this vital role, it is important to clarify physiological information about macroalgae as it reflects their growth potential in the field. In this study, we examined the biomass, pigment content, and photosynthetic O2 evolution rate versus irradiance curves of 18 macroalgal species from the intertidal zone of the Guangdong–Hong Kong–Macao Greater Bay Area, China, and investigated their photosynthetic patterns in relation to phyla characteristics, morphology, and growth locations. The results showed that green algae had the highest maximum photosynthetic O2 evolution rate (Pmax), light utilization efficiency (α), and dark respiration (Rd) among the three macroalgal phyla; the sheet-like macroalgal species had the highest Pmax, α, and Rd among the four morphological categories. The macroalgal species in the upper intertidal zone showed higher Pmax and α and lower saturation irradiance (EK) and compensation irradiance (EC) than those species in the lower intertidal location. The PCA results showed that the biomass of sheet-like macroalgal species was positively correlated with factor PC1 (50.34%), and that of finely branched species was negatively correlated with factor PC2 (25.17%). In addition, our results indicate that the light absorption and utilization capabilities of macroalgae could determine whether they could dominate the intertidal zone and that their photosynthetic characteristics could be used as a potential indicator of their biomass distribution in the Greater Bay Area.

Co-transport of biochar nanoparticles (BC NPs) and rare earth elements (REEs) in water-saturated porous media: New insights into REE fractionation - Quan Wan; Beibei Liu; Miaoyue Zhang; Man Zhao; Yuan Dai; Wenshen Liu; Kengbo Ding; Qingqi Lin; Zhuobiao Ni; Jingjing Li; Shizhong Wang; Chao Jin; et al. (Journal of Hazardous Materials, 2023)

Phosphorus amendment alters soil arbuscular mycorrhizal fungal functional guild compositions in a subtropical forest - Quan-Cheng Wang; Sheng-Sheng Jin; Shanshan Liu; Ge Song; Chunjian Duan; Peng-Peng Lü; Pulak Maitra; Lin Xie; Yongxin Lin; Hang-Wei Hu; Ji-Zheng He; Yong Zheng (Journal of Soils and Sediments, 2023)

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Sub-inhibitory concentrations of ampicillin affect microbial Fe(III) oxide reduction - Guiqin Yang; Tiqun Hou; Annian Lin; Xue Xia; Xiaoyun Quan; Zhili Chen; Li Zhuang (Journal of Hazardous Materials, 2023)

Rapid quantitative detection of okadaic acid in shellfish using lanthanide-labelled fluorescent-nanoparticle immunochromatographic test strips - Xiaomei Wang; Chen Yang; Wei Jiang; Manyu Zhang; Ruifang Li; Yajuan Lin; Quan Wang (Food Control, 2023)

Correlation between tumor cell migration and formaldehyde levels revealed by fluorescence imaging - Wei Quan; Yanxia Li; Wenhui Song; Zihong Li; Qian Zhang; Weiying Lin (Chemical Engineering Journal, 2023)

Using the solution of self-settling microalgae Scenedesmus obliquus as processing medium for hydrothermal liquefaction of biomass - Xin Xu; Xiaoyu Lin; Jingying Lin; Yijing Wu; Zeyuan Zhao; Quan (Sophia) He; Yulong Wu; Jie Yang (Biomass and Bioenergy, 2023)

LRT-CLUSTER: A New Clustering Algorithm Based on Likelihood Ratio Test to Identify Driving Genes - Chenxu Quan; Fenghui Liu; Lin Qi; Yun Tie (Interdisciplinary Sciences: Computational Life Sciences, 2023)

How do temperature and precipitation drive dengue transmission in nine cities, in Guangdong Province, China: a Bayesian spatio-temporal model analysis - Yi Quan; Yingtao Zhang; Hui Deng; Xing Li; Jianguo Zhao; Jianxiong Hu; Ruipeng Lu; Yihan Li; Qian Zhang; Li Zhang; Zitong Huang; Jiong Wang; et al. (Air Quality, Atmosphere & Health, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Nano aluminum-based hybrid flocculant: Synthesis, characterization, application in mine drainage, flocculation mechanism - Zhiwei Lin; Chunhui Zhang; Yufeng Hu; Peidong Su; Bingxu Quan; Xuezhi Li; Zhao Zhang (Journal of Cleaner Production, 2023)

Construction of a spatially gridded heat flux map based on airborne flux Measurements using remote sensing and machine learning methods - Yibo Sun; Li Jia; Qiting Chen; Xingwen Lin; Bilige Sude; Zhanjun Quan; Ronald W.A. Hutjes (Agricultural and Forest Meteorology, 2023)

Quantitative morphometric analysis of a deep-water channel in the Taranaki Basin, New Zealand - Wei Wu; Guangxu Wang; Changsong Lin; Weiqing Liu; Quan Li; Zhendong Feng; Shuyuan Ning (Acta Oceanologica Sinica, 2023)

The ginsenoside Rh2 protects porcine oocytes against aging and oxidative stress by regulating SIRT1 expression and mitochondrial activity - Hongye Liu; Zhi-Yong An; Zhou-Yan Li; Liu-Hui Yang; Xiu-Li Zhang; Yan-Tong Lv; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2023)

Ambient temperature and nervous system diseases-related mortality in Japan from 2010 to 2019: A time-stratified case-crossover analysis - Szu Yu Lin; Chris Fook Sheng Ng; Yoonhee Kim; Zin Wai Htay; Alton Quan Cao; Rui Pan; Masahiro Hashizume (Science of The Total Environment, 2023)

Evaluation of passive envelope systems with radiative sky cooling and thermally insulated glazing materials for cooling - Jianheng Chen; Quan Gong; Lin Lu (Journal of Cleaner Production, 2023)

Liver Transcriptome Analysis Reveals Energy Regulation and Functional Impairment of Onychostoma sima During Starvation - Chunna Chen; Bo Zhou; Jue Lin; Quan Gong; Fei Xu; Zhengyi Li; Yingying Huang (Marine Biotechnology, 2023)

Correction to: Matrine suppresses expression of adhesion molecules and chemokines as a mechanism underlying its therapeutic effect in CNS autoimmunity - Quan-Cheng Kan; Lin Zhu; Nan Liu; Guang-Xian Zhang (Immunologic Research, 2023)

Anisotropic creep behavior of soft-hard interbedded rock masses based on 3D printing and digital imaging correlation technology - Yun Tian; Fa-quan Wu; Hong-ming Tian; Zhe Li; Xiao-yun Shu; Lin-kai He; Man Huang; Wei-zhong Chen (Journal of Mountain Science, 2023)

On-road mobile mapping of spatial variations and source contributions of ammonia in Beijing, China - Weiwei Pu; Jiujiang Sheng; Ping Tian; Mengyu Huang; Xiangxue Liu; Jeffrey L. Collett; Ziming Li; Xiujuan Zhao; Di He; Fan Dong; Nannan Zhang; Weijun Quan; et al. (Science of The Total Environment, 2023)

Experimental and numerical simulation study on thermal decomposition model of ammonium nitrate - Lin-Quan Gong; Jia-Jia Jiang; Jun-hui Gong; Yong Pan; Jun-Cheng Jiang (Process Safety and Environmental Protection, 2023)

Influence of plants on anammox process in constructed Wetland: Irrelevance, inhibition or enhancement - Jie Li; Lin Liu; Yu-Ming Zheng; Lin Ma; Quan-Bao Zhao; Xuan Wang; Chao-Xiang Liu (Chemical Engineering Journal, 2023)

Low-intensity pulsed ultrasound enhances immunomodulation and facilitates osteogenesis of human periodontal ligament stem cells by inhibiting the NF-κB pathway - Haiyan Lin; Qing Wang; Chuntian Quan; Qingyuan Ren; Wulin He; Hui Xiao (Cell and Tissue Banking, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

A novel monoclonal antibody efficiently blocks the infection of duck adenovirus 3 by targeting Fiber-2 - Yun Lin; Wenyuan Zhang; Jing Xie; Quan Xie; Tuofan Li; Zhimin Wan; Hongxia Shao; Aijian Qin; Jianqiang Ye (Veterinary Microbiology, 2023)

Mining the synergistic effect in hydrothermal co-liquefaction of real feedstocks through machine learning approaches - Jie Yu; Xiaomei Zhong; Zhilin Huang; Xiaoyu Lin; Haiyong Weng; Dapeng Ye; Quan (Sophia) He; Jie Yang (Fuel, 2023)

The responses of mesophilic and thermophilic anaerobic digestion of municipal sludge to periodic fluctuation disturbance of organic loading rate - Zong-Lin Wu; Quan Zhang; Zi-Yuan Xia; Min Gou; Zhao-Yong Sun; Yue-Qin Tang (Environmental Research, 2023)

Origin of clay in granite intrusive contact zone and its influence on tunnel deformation and instability - Guo-Hua Zhang; Bo-Wen Zhang; Fei Tan; Zhong-Hou Liu; Jun-Peng Zou; Zhong-Zhi Xie; Jin-Quan Wu; Zhi-Ping Lin; Zhan-Rong Zhang (Engineering Geology, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

Marker-assisted breeding of rice lines special for rice noodle-making by pyramiding the Wxg2 and ALKGC genes - Bin Teng; Fengshun Song; Quan Gan; Cuixiang Lin; Dahu Ni (Euphytica, 2023)

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Partitioning behavior-oriented health risk assessment on internal organophosphorus flame retardants exposure - Quan Zhang; Mengjie Chu; Shu Lin; Jianlin Lou; Cui Wang (Environmental Research, 2023)

Effects of exposure to phthalate during early pregnancy on gestational diabetes mellitus: a nested case–control study with propensity score matching - Wei Chen; Caidie He; Xiang Liu; Songlin An; Xia Wang; Lin Tao; Haonan Zhang; Yingkuan Tian; Nian Wu; Pei Xu; Dengqing Liao; Juan Liao; et al. (Environmental Science and Pollution Research, 2022)

Spatial–temporal variations and pollution risks of mercury in water and sediments of urban lakes in Guangzhou City, South China - Xiaojun Wang; Wei Zhong; Bingxiang Wang; Mingying Quan; Tianhang Li; Durui Lin; Shengtan Shang; Chan Zhu; Churan Zhang; Yiling Liao (Environmental Science and Pollution Research, 2022)

Long‐term drought aggravates instability of alpine grassland productivity to extreme climatic event - Yun L. He; Jin S. Wang; Da S. Tian; Quan Quan; Lin Jiang; Fang F. Ma; Lu Yang; Fang Y. Zhang; Qing P. Zhou; Shu L. Niu (Ecology, 2022)
The frequency and severity of extreme weather events are increasing and expected to increase more in the future, together with global change. However, how extreme events and global change factors interactively influence community structures and ecosystem processes is largely unknown. Here, we investigated the responses of the temporal stability and resilience of aboveground net primary productivity (ANPP) of an alpine meadow to an extreme flooding event under different treatments of experimental drought and clipping. We found that ecosystems that were exposed to drought treatments for 3 years significantly decreased the temporal stability of community productivity but increased resilience to flooding, whereas their resistance to or recovery from flooding did not change. Neither clipping nor its interaction with drought altered the responses of these community stability metrics to flooding. Drought treatments significantly decreased plant species richness and asynchrony and dominant species stability, leading to a decrease in temporal stability and an increase in resilience in response to the extreme flooding event. The study also revealed that the change in species asynchrony was the dominant impact pathway determining the responses of resilience and temporal stability to flooding. Our results highlight that alpine grassland that experiences a multiyear drought may aggravate the instability of community productivity to extreme climatic events by reducing species asynchrony.

Tea consumption and cerebral hemorrhage risk: a meta-analysis - Pengfei Cheng; Junxiang Zhang; Wenting Liu; Quan Sun; Zhaoxin Fu; Hao Lin; Sheng Bi; Jiaying Zhu (Acta Neurologica Belgica, 2022)

Microbial transformation of distinct exogenous substrates into analogous composition of recalcitrant dissolved organic matter - Jie Lian; Xiaoxuan Zheng; Xiaocun Zhuo; Yi‐Lung Chen; Chen He; Qiang Zheng; Ta‐Hui Lin; Jia Sun; Weidong Guo; Quan Shi; Nianzhi Jiao; Ruanhong Cai (Environmental Microbiology, 2022)

Polyethylene microplastic exposure and concurrent effect with Aeromonas hydrophila infection on zebrafish - Ning Ding; Lin Jiang; Xiao Wang; Chun Wang; Yue Geng; Jianxin Zhang; Yingxue Sun; Yanping Zhang; Quan Yuan; Hong Liu (Environmental Science and Pollution Research, 2022)

Ancylostoma ceylanicum Infection in a Miniature Schnauzer Dog Breed - Xu-Hui Lin; Hai-Ming Cai; Zhuan-Qiang Yan; Shen-Quan Liao; Min-Na Lv; Cai-Yan Wu; Juan Li; Jun-Jing Hu; Wen-Wan Xiao; Jian-Fei Zhang; Nan-Shan Qi; Ming-Fei Sun (Acta Parasitologica, 2022)

Coastal aquaculture farms for the sea cucumber Apostichopus japonicus provide spawning and first-year nursery grounds for wild black rockfish, Sebastes schlegelii: A case study from the Luanhe River estuary, Bohai bay, the Bohai Sea, China - Min Xu; Zun-li Qi; Zun-lei Liu; Wei-min Quan; Qi Zhao; Yun-ling Zhang; Hui Liu; Lin-lin Yang (Frontiers in Marine Science, 2022)
Aquaculture farms are known to attract wild organisms from nearby areas. Sea cucumber Apostichopus japonicus aquaculture farms in Bohai Bay, the Bohai Sea, China, might provide spawning and nursery grounds for wild black rockfish Sebastes schlegelii populations. To identify the above, we studied the variation in the numbers of S. schlegelii larvae (and length-categories as a percentage of the natural population) via ichthyoplankton surveys by months from January to October 2020, and assessed the food web structure and energy flow distribution of the farm and trophic links of S. schlegelii natural stock by using Ecopath modeling in July 2016 to August 2017. Larvae with a length between 3.90-5.80 mm were observed in the farm in May 2020, the juveniles with an estimated trophic level of 4.31. Juveniles used the farms as first-year nursery ground, and then they swam into deeper waters in August of the following year. MTI analysis showed increasing biomass of S. schlegelii might result in a decrease in the biomass of crustacea, and had positive and negative impacts on mollusk and Hexagrammos otakii biomass. We argued that aquacultural infrastructures constructed by artificial reefs could be used as a fisheries management tool to enhance S. schlegelii stocks and that monitoring of other marine organisms, such as oysters, Rapana venosa , Charybdis japonica , and Asterias spp. etc., was necessary to maintain sustainable exploitations of aquacultural farm ecosystems. A paucity of knowledge surrounding the interactions between aquaculture farms and wild organisms needs furthermore researches.

Lignans and phenylpropanoids from the roots of Ficus hirta and their cytotoxic activities - Xian-Sheng Ye; Wen-Jing Tian; Xiang-Zhong Liu; Mi Zhou; De-Quan Zeng; Ting Lin; Guang-Hui Wang; Xin-Sheng Yao; Hai-Feng Chen (Natural Product Research, 2022)

The IRE1/JNK signaling pathway regulates inflammation cytokines and production of glomerular extracellular matrix in the acute kidney injury to chronic kidney disease transition - Yan Liang; Lingyun Qu; Zhenjie Liu; Lulu Liang; Yingzi Wang; Songxia Quan; Yulin Wang; Lin Tang (Molecular Biology Reports, 2022)

Characteristics and comparative analysis of Mesona chinensis Benth chloroplast genome reveals DNA barcode regions for species identification - Danfeng Tang; Yang Lin; Fan Wei; Changqian Quan; Kunhua Wei; Yanyan Wei; Zhongquan Cai; Muhammad Haneef Kashif; Jianhua Miao (Functional & Integrative Genomics, 2022)

Impact of air pollutants on hospital visits for pediatric asthma in Fuzhou city, southeast China - Quan Zhou; Shu-Ling Kang; Xin Lin; Xiao-Yang Zhang (Environmental Science and Pollution Research, 2022)

Correction to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2022)

Effects of dietary nucleotides on growth performance, immune response, intestinal morphology and disease resistance of juvenile largemouth bass, Micropterus salmoides - Xiao‐chun Chen; Xiao‐quan Huang; Yi‐wen Tang; Lei Zhang; Feng Lin (Journal of Fish Biology, 2022)
An 8 week feeding trial was carried out to investigate the effects of dietary nucleotides on growth performance, intestinal morphology, immune response and disease resistance of juvenile largemouth bass, Micropterus salmoides . Five grades of dietary nucleotide levels were designed as 0, 0.2, 0.4, 0.8 and 1.2 g kg −1 , respectively. Each group had 3 replicates, with 40 fish in each replicate. After the feeding experiment, 15 fish from each tank were infected with Aeromonas hydrophila for 14 days. The results indicated that fish fed the diets containing 0.4, 0.8 and 1.2 g kg −1 nucleotides had higher growth performance and feed utilization than those fed the control diet. Nonetheless, there were no significant differences in survival between all the groups, although fish fed the diets with all‐level nucleotides obtained higher survival than those fed the control diet. Dietary nucleotides significantly affected the superoxide dismutase, acid phosphatase and catalase activities in serum but not the malondialdehyde content. Fish fed the 0.4 g kg −1 nucleotide diets had the highest fold height, enterocyte height and muscular layer thickness significantly. The average mortality of largemouth bass infected with A. hydrophila was significantly influenced by dietary nucleotides. The mortality was significantly higher in the control group (91.11%) and 0.02% nucleotide group (73.11%) followed by the other groups and lowest in the 0.8 g kg −1 nucleotide group. In summary, dietary 0.4–0.8 g kg −1 nucleotides promoted growth performance, enhanced immunity and improved intestinal morphology and disease resistance of largemouth bass.

Sesquiterpene lactones from Carpesium abrotanoides L. and their activity in inducing protective autophagy - Bao-Jia Yang; Juan Wang; Zheng-Quan Zeng; Xu Yang; Ai-Ying Huang; Xiao-Jiang Hao; Xiao Ding; Shun-Lin Li (Natural Product Research, 2022)

Flow-slide characteristics and failure mechanism of shallow landslides in granite residual soil under heavy rainfall - Hui-lin Bai; Wen-kai Feng; Shuang-quan Li; Long-zhen Ye; Zhong-teng Wu; Rui Hu; Hong-chuan Dai; Yun-peng Hu; Xiao-yu Yi; Peng-cheng Deng (Journal of Mountain Science, 2022)

Comparative transcriptome analysis provides insight into the molecular mechanisms of long-day photoperiod in Moringa oleifera - Mengfei Lin; Shiying Ma; Kehui Quan; Endian Yang; Lei Hu; Xiaoyang Chen (Physiology and Molecular Biology of Plants, 2022)

Analysis of the influence of reinforcement material type on bearing and deformation characteristics of reinforced earth retaining wall - Jia-Quan Wang; Sen-Lei Hou; Zhi-Nan Lin; Yi Tang (Arabian Journal of Geosciences, 2022)

Differences of Macroalgal Consumption by Eight Herbivorous Coral Reef Fishes From the Xisha Islands, China - Peng Wu; Teng Wang; Yong Liu; Chunhou Li; Yayuan Xiao; Shannan Xu; Tingting Han; Lin Lin; Qiumei Quan (Frontiers in Marine Science, 2022)
Herbivorous fishes play an important role in preventing the overabundance of macroalgae on coral reefs. Understanding the feeding selectivity and consumption of macroalgae by herbivorous fishes can be challenging in studies of their ecological role in the preservation and recovery of coral reefs. Coral reef decline, macroalgal overgrowth and overfishing are clearly visible in the Xisha Islands, China. However, there are seldom studies on the feeding behaviors of herbivorous fishes in this area. We used microscopy, 18S rRNA high-throughput sequencing, and stable isotope analyses to comprehensively examine the diet of eight herbivorous reef fish species common in the Xisha Islands, including one parrotfish, two chub, two unicorn fish, and three rabbitfish. Based on microscopic examination, Siganus argenteus fed on the highest number of macroalgae species (five species), followed by Naso unicornis (four species). Kyphosus cinerascens , K. vaigiensis , N. unicornis and S. punctatissimus fed on the entire macroalgal thallus, indicating their greater ecological importance compared with species that only consume algal fronds. According to the 18S rRNA high-throughput sequencing of fish intestinal contents, cluster analysis revealed that consumed macroalgae composition from the eight fishes always grouped together based on the fish species, but with low similarity. K. vaigiensis removed the highest diversity of macroalgae species as well as the greatest quantity of macroalgae. Calotomus carolinus can consume the red alga Pneophyllum conicum , which is widely distributed on Indo-Pacific coral reefs and can overgrow and kill live corals. N. unicornis was found to occupy the lowest trophic position based on stable isotope analysis. Multi-technique analyses revealed that K. vaigiensis , N. unicornis and S. argenteus showed a high consumption potential of macroalgae, suggesting that they are the key browsers that should receive priority protection in the Xisha Islands. A diverse herbivorous fish fauna is also very important in the Xisha coral reefs. These results not only demonstrated the various functions of different herbivorous fish species in macroalgal removal, but also provided insights into the management of herbivorous fishes on the coral reefs of the South China Sea.

TRIP13 knockdown inhibits the proliferation, migration, invasion, and promotes apoptosis by suppressing PI3K/AKT signaling pathway in U2OS cells - De-Chen Yu; Xiang-Yi Chen; Hai-Yu Zhou; De-Quan Yu; Xiao-Lei Yu; Yi-Cun Hu; Rui-Hao Zhang; Xiao-Bo Zhang; Kun Zhang; Mao-Qiang Lin; Xi-Dan Gao; Tao-Wen Guo (Molecular Biology Reports, 2022)

Isolation and characterization of 34 SNP markers in Acipenser baerii - Quan Gong; Qingzhi Li; Jiahua Sun; Yu Xiao; Xutao Su; Guangxun Liu; Jun Du; Jue Lin (Conservation Genetics Resources, 2022)

Detection of pulmonary tuberculosis in children using the Xpert MTB/RIF Ultra assay on sputum: a multicenter study - Xiaoshan Peng; Qiong Liao; Min Fang; Yu Zhu; Yan Shi; Shuting Quan; Yacui Wang; Li Duan; Xiaomei Shi; Yang Liu; Manzhi Wang; Qingsong Wei; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Individual exposure to ambient PM2.5 and hospital admissions for COPD in 110 hospitals: a case-crossover study in Guangzhou, China - Jie-Qi Jin; Dong Han; Qi Tian; Zhao-Yue Chen; Yun-Shao Ye; Qiao-Xuan Lin; Chun-Quan Ou; Li Li (Environmental Science and Pollution Research, 2022)
Few studies have evaluated the short-term association between hospital admissions and individual exposure to ambient particulate matter (PM 2.5 ). Particularly, no studies focused on hospital admissions for chronic obstructive pulmonary disease (COPD) at the individual level. We assessed the short-term effects of PM 2.5 on hospitalization admissions for COPD in Guangzhou, China, during 2014–2015, based on satellite-derived estimates of ambient PM 2.5 concentrations at a 1-km resolution near the residential address as individual-level exposure for each patient. Around 40,002 patients with COPD admitted to 110 hospitals were included in this study. A time-stratified case-crossover design with conditional logistic regression models was applied to assess the effects of PM 2.5 based on a 1-km grid data of aerosol optical depth provided by the National Aeronautics and Space Administration on hospital admissions for COPD. Further, we performed stratified analyses by individual demographic characteristics and season of hospital admission. Around 10 μg/m 3 increase in individual-level PM 2.5 was associated with an increase of 1.6% (95% confidence interval [CI]: 0.6%, 2.7%) in hospitalization for COPD at a lag of 0–5 days. The impact of PM 2.5 on hospitalization for COPD was greater significantly in males and patients admitted in summer. Our study strengthened the evidence for the adverse effect of PM 2.5 based on satellite-based individual-level exposure data.

Bioinformatics-based study to identify immune infiltration and inflammatory-related hub genes as biomarkers for the treatment of rheumatoid arthritis - Sheng Fang; Xin Xu; Lin Zhong; An-quan Wang; Wei-lu Gao; Ming Lu; Zong-Sheng Yin (Immunogenetics, 2021)

Conservation planning on China's borders with Myanmar, Laos, and Vietnam - Lin Wang; Bin Yang; Yang Bai; Xiaoqiang Lu; Richard T. Corlett; Yunhong Tan; Xiao‐Yong Chen; Jianguo Zhu; Yan Liu; Rui‐Chang Quan (Conservation Biology, 2021)
Transboundary conservation is playing an increasingly important role in maintaining ecosystem integrity and halting biodiversity loss caused by anthropogenic activities. However, lack of information on species distributions in transboundary regions and understanding of the threats in these areas impairs conservation. We developed a spatial conservation plan for the transboundary areas between Yunnan province, southwestern China, and neighboring Myanmar, Laos, and Vietnam in the Indo‐Burma biodiversity hotspot. To identify priority areas for conservation and restoration, we determined species distribution patterns and recent land‐use changes and examined the spatiotemporal dynamics of the connected natural forest, which supports most species. We assessed connectivity with equivalent connected area (ECA), which is the amount of reachable habitat for a species. An ECA incorporates the presence of habitat in a patch and the amount of habitat in other patches within dispersal distance. We analyzed 197,845 locality records from specimen collections and monographs for 21,004 plant and vertebrate species. The region of Yunnan immediately adjacent to the international borders had the highest species richness, with 61% of recorded species and 56% of threatened vertebrates, which suggests high conservation value. Satellite imagery showed the area of natural forest in the border zone declined by 5.2% (13,255 km 2 ) from 1995 to 2018 and monoculture plantations increased 92.4%, shrubland 10.1%, and other cropland 6.2%. The resulting decline in connected natural forest reduced the amount of habitat, especially for forest specialists with limited dispersal abilities. The most severe decline in connectivity was along the Sino‐Vietnamese border. Many priority areas straddle international boundaries, indicating demand and potential for establishing transboundary protected areas. Our results illustrate the importance of bi‐ and multilateral cooperation to protect biodiversity in this region and provide guidance for future conservation planning and practice.

Correction to: Biomimetic Biphasic Electrospun Scaffold for Anterior Cruciate Ligament Tissue Engineering - Ya Tang; Jialiang Tian; Long Li; Lin Huang; Quan Shen; Shanzhu Guo; Yue Jiang (Tissue Engineering and Regenerative Medicine, 2021)

Biomimetic Biphasic Electrospun Scaffold for Anterior Cruciate Ligament Tissue Engineering - Ya Tang; Jialiang Tian; Long Li; Lin Huang; Quan Shen; Shanzhu Guo; Yue Jiang (Tissue Engineering and Regenerative Medicine, 2021)

Enhancement of Osteogenic Induction by LL37 Modified with a Collagen-Binding Domain In Vitro and In Vivo - Xiaoxuan Lin; Sipeng Chen; Jingjing Quan; Qi Zhang; Muzi Liao; Xinyue Ma; Yuyan Zheng; Sui Mai (International Journal of Peptide Research and Therapeutics, 2021)

Optimization of ultrasound and microwave-assisted extraction of sweet cherry tree branches and chemical component analysis by UPLC–MS/MS - Huimin Zhang; Hongguang Yan; Cuixiang Lu; Hui Lin; Quan Li (Trees, 2021)

Correction to: Nexus between agro-ecological efficiency and carbon emission transfer: evidence from China - Usman Akbar; Quan-Lin Li; Muhammad Abdullah Akmal; Mohammed Shakib; Wasim Iqbal (Environmental Science and Pollution Research, 2021)

N6-methyladenine DNA Demethylase ALKBH1 Regulates Mammalian Axon Regeneration - Qiao Li; Cheng Qian; Harry Feng; Tyger Lin; Qingsan Zhu; Ying Huang; Feng-Quan Zhou (Neuroscience Bulletin, 2021)

Identification of Regeneration and Hub Genes and Pathways at Different Time Points after Spinal Cord Injury - Sheng Fang; Lin Zhong; An-quan Wang; Hui Zhang; Zong-Sheng Yin (Molecular Neurobiology, 2021)

Late Jurassic Maofengshan two‐mica granites in Guangzhou, South China: fractional crystallization products of metasedimentary‐rock‐derived magmas - Xiao Liu; Qiang Wang; Lin Ma; Guo-Ning Gou; Quan Ou; Jun Wang (Mineralogy and Petrology, 2021)

Kelp aquaculture in China: a retrospective and future prospects - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
Globally, China has the largest scale of kelp cultivation and production operations. However, its kelp aquaculture industry is suffering from declining germplasm diversity, degradation of agronomic traits, the presence of polluted environments, changing ocean conditions and increasing anthropological interference. This review covers two of the most commercially important kelp species in China, viz. Saccharina japonica and Undaria pinnatifida . It summarizes the history of their cultivation, production, economic and ecological benefits, their breeding programmes (e.g. inter‐ and intra‐specific hybridization and marker‐assisted selection) and efforts towards population genetic diversity and conservation. The article focuses on three significant challenges, for example genetic cross‐contamination between the wild and farmed kelp populations, ocean warming and ocean acidification. Accordingly, we outline the steps required to provide several intervention measures, for example (i) collection and preservation of wild and cultivated kelp germplasm; (ii) selection of suitable cultivation sites under changing environmental conditions; (iii) developing stress‐resistant cultivars; and finally, (iv) adoption of innovative cultivation models. The review concludes with genome‐based, designs for molecular breeding and calls for the establishment of an East Asian Kelp Consortium (EAKC). Collectively, the Chinese kelp industry could provide beneficial goods and services, for example bioenergy to fine chemicals and environmental benefits, such as carbon capture, pH amelioration and provision of habitat for many other marine species of commercial value. The strategies proposed in this article thus have the potential to not only improve but also reinvigorate the kelp industry in China and nearby Japan and Korea, in the context of both environmental health and economic benefits.

Cover Image - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
The cover image is based on the Review Article Kelp aquaculture in China: A retrospective and future prospects by Zi‐Min Hu et al., https://doi.org/10.1111/raq.12524 . image

PtP38 May Increase the Immune Ability of Portunus trituberculatus Stimulated by LPS Imitating a Gram-Negative Bacterial Infection - Cheng-Peng Lu; Chao-Guang Wei; Jun-Quan Zhu; Dao-Jun Tang; Chun-Lin Wang; Cong-Cong Hou (Frontiers in Marine Science, 2021)
The P38 mitogen-activated protein kinase (MAPK) signal transduction pathway is widespread in organisms and plays important roles in immune activities. The infection mechanism of environmental gram-negative bacteria on crustaceans is an important scientific problem. In this study, the cDNA full-length sequence of Portunus trituberculatus P38 (PtP38) was cloned and its structure was analyzed by bioinformatics methods. To study the function of the PtP38 gene after a Gram-negative bacterial infection, we injected P. trituberculatus with LPS to activate the immune response instead of directly infecting with Gram-negative bacteria. With LPS stimulation, the expression of the PtP38 gene in different tissues increased significantly. At the same time, the expression of immune-related genes (ALF and crustin) in the hepatopancreas, activities of antioxidant enzymes [superoxide dismutase (SOD), catalase (CAT), and inducible nitric oxide synthase (iNOS) enzymes], and expression of apoptosis-related genes (caspase2 and caspase3) were increased significantly. To further conform the function of PtP38 in the immune response, we injected P. trituberculatus with P38 inhibitor and subsequently injected with LPS. The results showed that the expression of immune-related genes was inhibited, the activity of antioxidant enzymes was decreased, and the expression of apoptosis-related genes were inhibited. Thus, we speculated that PtP38 may increase the immune ability by improving the expression of antimicrobial peptides, increasing the activity of oxidative stress-related enzymes, and promoting cell apoptosis in infected P. trituberculatus . This study also laid the foundation for further study of the P38 MAPK signaling pathway and immune mechanism of P. trituberculatus .

MiR-124 and Small Molecules Synergistically Regulate the Generation of Neuronal Cells from Rat Cortical Reactive Astrocytes - Yangyang Zheng; Zhehao Huang; Jinying Xu; Kun Hou; Yifei Yu; Shuang Lv; Lin Chen; Yulin Li; Chengshi Quan; Guangfan Chi (Molecular Neurobiology, 2021)

Microbial transformation of distinct exogenous substrates into analogous composition of recalcitrant dissolved organic matter - Jie Lian; Xiaoxuan Zheng; Xiaocun Zhuo; Yi‐Lung Chen; Chen He; Qiang Zheng; Ta‐Hui Lin; Jia Sun; Weidong Guo; Quan Shi; Nianzhi Jiao; Ruanhong Cai (Environmental Microbiology, 2021)
Summary Oceanic dissolved organic matter (DOM) comprises a complex molecular mixture which is typically refractory and homogenous in the deep layers of the ocean. Though the refractory nature of deep‐sea DOM is increasingly attributed to microbial metabolism, it remains unexplored whether ubiquitous microbial metabolism of distinct carbon substrates could lead to similar molecular composition of refractory DOM. Here, we conducted microbial incubation experiments using four typically bioavailable substrates (L‐alanine, trehalose, sediment DOM extract, and diatom lysate) to investigate how exogenous substrates are transformed by a natural microbial assemblage. The results showed that although each‐substrate‐amendment induced different changes in the initial microbial assemblage and the amended substrates were almost depleted after 90 days of dark incubation, the bacterial community compositions became similar in all incubations on day 90. Correspondingly, revealed by ultra‐high resolution mass spectrometry, molecular composition of DOM in all incubations became compositionally consistent with recalcitrant DOM and similar toward that of DOM from the deep‐sea. These results indicate that while the composition of natural microbial communities can shift with substrate exposures, long‐term microbial transformation of distinct substrates can ultimately lead to a similar refractory DOM composition. These findings provide an explanation for the homogeneous and refractory features of deep‐sea DOM.

GTree: an Open-source Tool for Dense Reconstruction of Brain-wide Neuronal Population - Hang Zhou; Shiwei Li; Anan Li; Qing Huang; Feng Xiong; Ning Li; Jiacheng Han; Hongtao Kang; Yijun Chen; Yun Li; Huimin Lin; Yu-Hui Zhang; et al. (Neuroinformatics, 2021)

Exendin-4 Reversed the PC12 Cell Damage Induced by circRNA CDR1as/miR-671/GSK3β Signaling Pathway - Hui Quan; Qiudan Chen; Kesheng Wang; Qinwan Wang; Meiling Lu; Yue Zhang; Sujing Qiang; Shaobo Xue; Lin Han; Huanhuan Zhu; Qiangyuan Fan; Meiyu Bao; et al. (Journal of Molecular Neuroscience, 2021)

RETRACTED ARTICLE: Nexus between agro-ecological efficiency and carbon emission transfer: evidence from China - Usman Akbar; Quan-Lin Li; Muhammad Abdullah Akmal; Mohammed Shakib; Wasim Iqbal (Environmental Science and Pollution Research, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

sgRNACNN: identifying sgRNA on-target activity in four crops using ensembles of convolutional neural networks - Mengting Niu; Yuan Lin; Quan Zou (Plant Molecular Biology, 2021)

Highly enriched N‐containing organic molecules of Synechococcus lysates and their rapid transformation by heterotrophic bacteria - Qiang Zheng; Wenxin Lin; Yu Wang; Yunyun Li; Chen He; Yuan Shen; Weidong Guo; Quan Shi; Nianzhi Jiao (Limnology and Oceanography, 2021)
Phytoplankton are major contributors of labile dissolved organic matter to marine euphotic zone ecosystems. Viral‐mediated phytoplankton lysis releases a considerable amount of bioavailable cellular contents and facilitates localized heterotrophic bacterial growth. The rapid turnover times of this labile organic matter renders it difficult to trace their transformation within natural environments. In the present study, we used a model phototroph‐heterotroph coculture system to investigate the organic molecular variation during cyanophage‐induced Synechococcus lysis and post‐lysis periods using fluorescence spectroscopy and ultrahigh resolution mass spectrometry analyses. Approximately 80% of the Synechococcus lysates were respired to carbon dioxide within 2 days coupled to rapid regeneration of inorganic nutrients. Five fluorescent dissolved organic matter components were detected in the incubations including four humic‐like and one protein‐like components, and their abundances varied markedly with the succession of the viral lysis process. Viral lysis promoted the transformation of Synechococcus biomass to dissolved organic matter, and heterotrophic bacterial metabolism facilitated the transformation of organic molecules from relatively high (avg. ~ 430 Da) to low (avg. ~ 360 Da) molecular weight, corresponding to variation in their bioavailability. The Synechococcus ‐derived organic matter was highly enriched in N‐containing organic molecules. Identified metabolites within the cultures primarily comprised amino acids or oligopeptides and other low‐molecular‐weight organic acids, carbohydrates, nucleotides, lipids, biogenic amines, and porphyrins. Among these, oligopeptides, nucleotides, and lipid compounds significantly increased with viral lysis. These results provide insight into biogeochemical cycling mediated by viral shunts in oceans, thus deepening our understanding of microbial food webs at the molecular level.

Channelized and unchannelized collapses of granular columns on a horizontal surface - Quan Zhang; Bo-lin Huang; Hai-lin Zhao; Xiao-ting Chen; Chao-lin Luo (Journal of Mountain Science, 2020)

Complete mitochondrial genome of the freshwater fish Acrossocheilus longipinnis (Teleostei: Cyprinidae): genome characterization and phylogenetic analysis - Xiao-Jing Hou; Hung-Du Lin; Wen-Qiao Tang; Dong Liu; Chiao-Chuan Han; Jin-Quan Yang (Biologia, 2020)

Evaluation of the Impacts of Formulation Parameters on the Pharmacokinetics and Bioequivalence of Risperidone Orodispersible Film: a Physiologically Based Pharmacokinetic Modeling Approach - Fang Chen; Hongrui Liu; Bing Wang; Zhou Yang; Yusheng Chen; Liuliu Yang; Bing Wang; Zheng Jiao; Hai-Shu Lin; Yingjun Quan; Hao Wang; Xiaoqiang Xiang (AAPS PharmSciTech, 2020)

RES transformation for biosynthesis and detoxification - Jin-Quan Huang; Jia-Ling Lin; Xiao-Xiang Guo; Xiu Tian; Ye Tian; Xiao-Xia Shangguan; Ling-Jian Wang; Xin Fang; Xiao-Ya Chen (Science China Life Sciences, 2020)

Association Between PSD95 Gene 3′UTR Single Nucleotide Polymorphism and Risk of Acute Ischemic Stroke in Chinese Han Population - Ying-Ying Lin; Tong-ya Yu; Hui Quan; Yu-Juan Chen; Xue-Yuan Liu; Dong-Ya Huang (Journal of Molecular Neuroscience, 2020)

Microseismic Monitoring to Characterize Structure-Type Rockbursts: A Case Study of a TBM-Excavated Tunnel - Quan-Sheng Liu; Jian Wu; Xiao-Ping Zhang; Lie-Xian Tang; Chen Bi; Wei-Wei Li; Jin-Lin Xu (Rock Mechanics and Rock Engineering, 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

A remote sensing monitoring method for alpine grasslands desertification in the eastern Qinghai-Tibetan Plateau - Qian Kuang; Quan-zhi Yuan; Ji-chong Han; Rong Leng; Yu-shuang Wang; Ke-hong Zhu; Shuo Lin; Ping Ren (Journal of Mountain Science, 2020)

Chemical constituents from the deep sea-derived Streptomyces xiamenensis MCCC 1A01570 and their effects on RXRα transcriptional regulation - Wei-Xiang Lin; Chun-Lan Xie; Mi Zhou; Man-Li Xia; Ting-Ting Zhou; Hai-Feng Chen; Xian-Wen Yang; Quan Yang (Natural Product Research, 2020)

Optimization and Evaluation of the Thermosensitive In Situ and Adhesive Gel for Rectal Delivery of Budesonide - Lin Chen; Xue Han; Xiaohong Xu; Quan Zhang; Yingchun Zeng; Qing Su; Yujie Liu; Yanmei Sheng; Xingliang Xie (AAPS PharmSciTech, 2020)

Satellite data cloud detection using deep learning supported by hyperspectral data - Lin Sun; Xu Yang; Shangfeng Jia; Chen Jia; Quan Wang; Xinyan Liu; Jing Wei; Xueying Zhou (International Journal of Remote Sensing, 2020)

The Effects of Winter Temperature and Land Use on Mangrove Avian Species Richness and Abundance on Leizhou Peninsula, China - Quan Chen; Guorui Xu; Zhifeng Wu; Peng Kang; Qian Zhao; Yuanqi Chen; Guangxuan Lin; Shuguang Jian (Wetlands, 2020)

Morphological characteristics and genetic diversity of Colletotrichum horii infecting persimmon tree in China - Quan-en Deng; Xiang-yang Ding; Jian-an Li; Lin-kai Cui; Jian-qiang Xu (European Journal of Plant Pathology, 2020)

Energy conversion and deposition behaviour in gravitational collapse of granular columns - Bo-lin Huang; Jian Wang; Quan Zhang; Chao-lin Luo; Xiao-ting Chen (Journal of Mountain Science, 2020)

Estimation of monthly pan evaporation using support vector machine in Three Gorges Reservoir Area, China - Ji-Long Chen; Hong Yang; Ming-Quan Lv; Zuo-Lin Xiao; Sheng Jun Wu (Theoretical and Applied Climatology, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Potassium ameliorates iron deficiency by facilitating the remobilization of iron from root cell walls and promoting its translocation from roots to shoots - Yi Quan Ye; Hong Yan Luo; Mao Li; Jia Jun Zhang; Guang Qiu Cao; Kai Min Lin; Si Zu Lin; Shan Shan Xu (Plant and Soil, 2019)

First Report on Toxoplasma gondii Seroprevalence in Free-Ranging Pigs in Northeastern China - Qi Li; Si-Yuan Qin; Shuo Li; Peng Peng; Quan Zhao; Hong-Lin Jia; Chun-Ren Wang (Acta Parasitologica, 2019)

Large-scale analysis of small RNAs derived from traditional Chinese herbs in human tissues - Fengming Huang; Jianchao Du; Zhu Liang; Zhichao Xu; Jiantao Xu; Yan Zhao; Yexuan Lin; Song Mei; Quan He; Jindong Zhu; Qiang Liu; Yanxu Zhang; et al. (Science China Life Sciences, 2019)

Polyphenol Removal from Sugarcane Juice by Using Magnetic Chitosan Composite Microparticles - Xing-quan Liang; Song-lin Fan; Jia-xing Zhang; Xiao-rong Song (Sugar Tech, 2019)

Experimental and numerical analyses on working performance of a high arch dam with deep-seated joints: Yebatan arch dam, China - Wen Zhang; Yuan Chen; Bao-quan Yang; Lin Zhang; Chong Zhang; Xiao-qiang Liu (Arabian Journal of Geosciences, 2019)

Novel Inhalable Ciprofloxacin Dry Powders for Bronchiectasis Therapy: Mannitol–Silk Fibroin Binary Microparticles with High-Payload and Improved Aerosolized Properties - Chunxia Liu; Ling Lin; Zhengwei Huang; Qiaoli Wu; Junhuang Jiang; Li Lv; Xiaoxia Yu; Guilan Quan; Guocheng Li; Chuanbin Wu (AAPS PharmSciTech, 2019)

The fecal virome of red-crowned cranes - Yan Wang; Shixing Yang; Dawei Liu; Chenglin Zhou; Wang Li; Yuan Lin; Xiaochun Wang; Quan Shen; Hua Wang; Chuang Li; Minghui Zong; Yuzhu Ding; et al. (Archives of Virology, 2019)

Study on Distribution Characteristics of Mining Stress and Elastic Energy Under Hard and Thick Igneous Rocks - Jin-quan Jiang; Quan-sen Wu; Quan-lin Wu; Pu Wang; Chen Zhang; Bin Gong (Geotechnical and Geological Engineering, 2018)

Contamination characteristics and potential environmental implications of heavy metals in road dusts in typical industrial and agricultural cities, southeastern Hubei Province, Central China - Da-Mao Xu; Jia-Quan Zhang; Bo Yan; Hao Liu; Li-Li Zhang; Chang-Lin Zhan; Li Zhang; Ping Zhong (Environmental Science and Pollution Research, 2018)

Evaluation of lead release potential of new premise plumbing materials - Iat-Leong Lei; Ding-Quan Ng; Shailesh S. Sable; Yi-Pin Lin (Environmental Science and Pollution Research, 2018)

Full-length and defective enterovirus G genomes with distinct torovirus protease insertions are highly prevalent on a Chinese pig farm - Yan Wang; Wen Zhang; Zhijian Liu; Xingli Fu; Jiaqi Yuan; Jieji Zhao; Yuan Lin; Quan Shen; Xiaochun Wang; Xutao Deng; Eric Delwart; Tongling Shan; et al. (Archives of Virology, 2018)

Interaction of MTHFR gene with smoking and alcohol use and haplotype combination susceptibility to psoriasis in Chinese population - Quan Luo; Jingxin Zeng; Wei Li; Ling Lin; Xin Zhou; Xin Tian; Weiyu Liu; Lidan Zhang; Xibao Zhang (Immunologic Research, 2018)

Modeling and multi-objective optimization for ANAMMOX process under COD disturbance using hybrid intelligent algorithm - Bin Xie; Yong-wen Ma; Jin-quan Wan; Yan Wang; Zhi-cheng Yan; Lin Liu; Ze-yu Guan (Environmental Science and Pollution Research, 2018)

Finite element response sensitivity analysis of three-dimensional soil-foundation-structure interaction (SFSI) systems - Quan Gu; Yongdou Liu; Yong Li; Chun Lin (Earthquake Engineering and Engineering Vibration, 2018)

CLDN6 enhances chemoresistance to ADM via AF-6/ERKs pathway in TNBC cell line MDAMB231 - Minlan Yang; Yanru Li; Yang Ruan; Yan Lu; Dongjing Lin; Yinping Xie; Bing Dong; Qihua Dang; Chengshi Quan (Molecular and Cellular Biochemistry, 2018)

Mitochondrial and nuclear genetic structure in Rhodeus ocellatus (Teleostei: Cyprinidae) with approximate Bayesian computation - Jin-Quan Yang; Kui-Ching Hsu; Po-Hsun Kuo; Lin-Lin Li; Wen-Qiao Tang; Dong Liu; Hung-Du Lin (Environmental Biology of Fishes, 2018)

Refined dynamic progressive collapse analysis of RC structures - You-Lin Xu; Yue Zheng; Quan Gu (Bulletin of Earthquake Engineering, 2018)

Surface wave attenuation based polarization attributes in time-frequency domain for multicomponent seismic data - Xuan-Lin Kong; Hui Chen; Zhi-Quan Hu; Jia-Xing Kang; Tian-Ji Xu; Lu-Ming Li (Applied Geophysics, 2018)

Effect of the dark septate endophytic fungus Acrocalymma vagum on heavy metal content in tobacco leaves - Hui-Qing Jin; Hua-Bing Liu; Ying-Ying Xie; Yong-Gang Zhang; Qing-Quan Xu; Li-Juan Mao; Xin-Jun Li; Jin Chen; Fu-Cheng Lin; Chu-Long Zhang (Symbiosis, 2018)

Erratum to: Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Matrine Treatment Blocks NogoA-Induced Neural Inhibitory Signaling Pathway in Ongoing Experimental Autoimmune Encephalomyelitis - Quan-Cheng Kan; Hui-Jun Zhang; Yuan Zhang; Xing Li; Yu-Ming Xu; Rodolfo Thome; Ming-Liang Zhang; Nan Liu; Yao-Juan Chu; Guang-Xian Zhang; Lin Zhu (Molecular Neurobiology, 2017)

Synthesis and biological evaluation of disulfides bearing 1,2,4-triazole moiety as antiproliferative agents - Xue-Feng Wang; Shuai Zhang; Bao-Lin Li; Ji-Jun Zhao; Yu-Ming Liu; Rui-Lian Zhang; Bo Li; Bao-Quan Chen (Medicinal Chemistry Research, 2017)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

α-Glucosidase inhibitors and phytotoxins from Streptomyces xanthophaeus - Jing Wei; Xiu-Yun Zhang; Shan Deng; Lin Cao; Quan-Hong Xue; Jin-Ming Gao (Natural Product Research, 2017)

In Situ Observation of Failure Mechanisms Controlled by Rock Masses with Weak Interlayer Zones in Large Underground Cavern Excavations Under High Geostress - Shu-Qian Duan; Xia-Ting Feng; Quan Jiang; Guo-Feng Liu; Shu-Feng Pei; Yi-Lin Fan (Rock Mechanics and Rock Engineering, 2017)

Construction and Identification of the RNAi Recombinant Lentiviral Vector Targeting Human DEPDC7 Gene - Zhijun Liao; Xinrui Wang; Dexin Lin; Quan Zou (Interdisciplinary Sciences: Computational Life Sciences, 2017)

An amplitude suppression method based on the decibel criterion - Xuan-Lin Kong; Hui Chen; Jin-Long Wang; Zhi-quan Hu; Dan Xu; Lu-Ming Li (Applied Geophysics, 2017)

RNA-Seq reveals differential expression patterns of genes associated with carotenoid accumulation in loquat - Ting-ting Zheng; Zhi-ke Zhang; Muhammad Qasim Shahid; Wei-ling Wei; Faheem Shehzad Baloch; Jin-cheng Wu; Shun-quan Lin; Xiang-hui Yang (Acta Physiologiae Plantarum, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

Simulating climate change impacts and potential adaptations on rice yields in the Sichuan Basin, China - Che-Chen Xu; Wen-Xiang Wu; Quan-Sheng Ge; Yang Zhou; Yu-Mei Lin; Ya-Mei Li (Mitigation and Adaptation Strategies for Global Change, 2017)

Potential Reproductive Advantage of Short-over Long-Winged Adult Males of the Cricket Velarifictorus ornatus - Lv-Quan Zhao; Huai-lin Chai; Dao-Hong Zhu (Evolutionary Biology, 2017)

Pilot-Scale Study on Treating Wastewater from Magnesium-Based Exhaust Gas Cleaning System by a Novel Process - Tie Li; Lin Sha; Quan Liu; Jiao Zhao; Xiaojia Tang; Yimin Zhu (Water, Air, & Soil Pollution, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

A novel bocavirus from domestic mink, China - Shixing Yang; Yan Wang; Wang Li; Zhaobin Fan; Lili Jiang; Yuan Lin; Xingli Fu; Quan Shen; Zixuan Sun; Xiaochun Wang; Xutao Deng; Wen Zhang; et al. (Virus Genes, 2016)

A study of sea level variability and its long-term trend in the South China Sea - Ying Xu; Mingsen Lin; Quan’an Zheng; Qingtao Song; Xiaomin Ye (Acta Oceanologica Sinica, 2016)

Brittle Rock Modeling Approach and its Validation Using Excavation-Induced Micro-Seismicity - Chun-Chi Ma; Tian-Bin Li; Hui-Lin Xing; Hang Zhang; Min-Jie Wang; Tian-Yi Liu; Guo-Qing Chen; Zi-Quan Chen (Rock Mechanics and Rock Engineering, 2016)

Radial propagation of magnetospheric substorm-injected energetic electrons observed using a BD-IES instrument and Van Allen Probes - QiuGang Zong; YiXin Hao; Hong Zou; SuiYan Fu; XuZhi Zhou; Jie Ren; LingHua Wang; ChongJing Yuan; ZhiYang Liu; XiangHong Jia; Lin Quan; Ying Liu; et al. (Science China Earth Sciences, 2016)

Biotransformation of gypenoside XVII to compound K by a recombinant β-glucosidase - Fei-Liang Zhong; Wei-Wei Dong; Songquan Wu; Jun Jiang; Deok-Chun Yang; Donghao Li; Lin-Hu Quan (Biotechnology Letters, 2016)

Multiscale partitioning of small mammal β‐diversity provides novel insights into the Quaternary faunal history of Qinghai–Tibetan Plateau and Hengduan Mountains - Zhixin Wen; Qisen Yang; Qing Quan; Lin Xia; Deyan Ge; Xue Lv (Journal of Biogeography, 2016)
Aim To assess the validity of four hypothesized drivers (Quaternary climate, niche conservatism, contemporary climate, spatial configuration) of small mammal beta diversity in the Qinghai–Tibetan Plateau ( QTP ) and the Hengduan Mountains ( HDM ). Location QTP and HDM of China. Methods We partitioned the beta diversity of small mammals in QTP and HDM into the spatial turnover and nestedness components at the regional (longitudinal/latitudinal zones) and grid (1° × 1°) scales. Regional beta diversity was evaluated by calculating the multiple‐site dissimilarities and the distance‐dissimilarity relationships. We examined the relative effects of geographical distance, environmental difference, habitat diversity, geographical isolation and Quaternary climate stability on the beta diversity patterns. Results The overall beta diversity in all longitudinal/latitudinal zones of both regions was primarily driven by spatial turnover, longitudinal nestedness patterns were almost non‐existent in QTP . Turnover was stronger in the latitudinal direction of QTP and in the longitudinal direction of HDM , which corresponded to the general topography of each region. At the grid scale, higher turnover was primarily concentrated in mountainous areas. Turnover was highly correlated with geographical distance and environmental difference in both regions, and geographical isolation was another strong predictor of turnover in HDM . Habitat diversity independently explained most of the variation in nestedness of HDM . Main conclusions Spatial turnover is the primary cause of the small mammal beta diversity in QTP and HDM . Three non‐exclusive mechanisms including the historic effect of past glaciation, contemporary climate and spatial configuration of the landscape might act in combination to shape the beta diversity patterns in QTP and HDM , particularly the directional patterns. Our results challenge the prevailing view that the current distribution of QTP fauna is primarily explained by westward post‐glacial recolonization, and support the alternative idea that QTP retained considerable refugia and even centres of origin during the Quaternary glaciations.

Reconstructing cephalopod migration with statolith elemental signatures: a case study using Dosidicus gigas - Bi Lin Liu; Jie Cao; Samuel B. Truesdell; Yong Chen; Xin Jun Chen; Si Quan Tian (Fisheries Science, 2016)

Mechanism Underlying the Analgesic Effect Exerted by Endomorphin-1 in the rat Ventrolateral Periaqueductal Gray - Tao Chen; Jing Li; Ban Feng; Rui Hui; Yu-Lin Dong; Fu-Quan Huo; Ting Zhang; Jun-Bin Yin; Jian-Qing Du; Yun-Qing Li (Molecular Neurobiology, 2016)

High Serum MiR-130a Levels Are Associated with Severe Perihematomal Edema and Predict Adverse Outcome in Acute ICH - Meng-Die Wang; Yong Wang; Yuan-Peng Xia; Jing-Wen Dai; Lin Gao; Si-Qi Wang; Hai-Jun Wang; Ling Mao; Man Li; Shi-Meng Yu; Yan Tu; Quan-Wei He; et al. (Molecular Neurobiology, 2016)

Functional analysis of PI-like gene in relation to flower development from bamboo (Bambusa oldhamii) - LONGFEI ZHU; YAN SHI; QIAOLU ZANG; QUAN SHI; SHINAN LIU; YINGWU XU; XINCHUN LIN (Journal of Genetics, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The substrate promiscuity of a phosphopantetheinyl transferase SchPPT for coenzyme A derivatives and acyl carrier proteins - Yue-Yue Wang; Hong-Dou Luo; Xiao-Sheng Zhang; Tao Lin; Hui Jiang; Yong-Quan Li (Archives of Microbiology, 2016)

Effects of simulated acid rain on microbial characteristics in a lateritic red soil - Hua-qin Xu; Jia-en Zhang; Ying Ouyang; Ling Lin; Guo-ming Quan; Ben-liang Zhao; Jia-yu Yu (Environmental Science and Pollution Research, 2015)

Tetramic acid derivatives and polyphenols from sponge-derived fungus and their biological evaluation - Jun-Feng Wang; Xiaochu Qin; Fu-Quan Xu; Tianyu Zhang; Shengrong Liao; Xiuping Lin; Bin Yang; Juan Liu; Lishu Wang; Zhengchao Tu; Yonghong Liu (Natural Product Research, 2015)

Crack propagation patterns and energy evolution rules of coal within slotting disturbed zone under various lateral pressure coefficients - Lin Bai-quan; Liu Ting; Zou Quan-le; Zhu Chuan-jie; Yan Fa-zhi; Zhang Zhen (Arabian Journal of Geosciences, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Identification of differentially expressed genes using digital gene expression profiles in Pyrus pyrifolia Nakai cv. Hosui bud release following early defoliation - Quan-jun Zhang; Shu-tian Tao; Meng Li; Xiao-xiao Qi; Jun Wu; Hao Yin; Jia-lin Deng; Shao-ling Zhang (Tree Genetics & Genomes, 2015)

Effect of igneous intrusions and normal faults on coalbed methane storage and migration in coal seams near the outcrop - Chuan-jie Zhu; Bai-quan Lin (Natural Hazards, 2015)

Single nucleotide polymorphisms in PDCD6 gene are associated with the development of cervical squamous cell carcinoma - Bin Zhou; Peng Bai; Hui Xue; Zhu Zhang; Shaoqing Shi; Kui Zhang; Yanyun Wang; Kana Wang; Yi Quan; Yaping Song; Lin Zhang (Familial Cancer, 2015)

Enrichment of cardiac differentiation by a large starting number of embryonic stem cells in embryoid bodies is mediated by the Wnt11-JNK pathway - Ming Chen; Cheng Qian; Lin-Lin Bi; Fang Zhao; Guang-Yu Zhang; Zhi-Quan Wang; Xue-Dong Gan; Yang-Gan Wang (Biotechnology Letters, 2015)

Spatiotemporal Dynamics of Salt Marsh Vegetation regulated by Plant Invasion and Abiotic Processes in the Yangtze Estuary: Observations with a Modeling Approach - Zhen-Ming Ge; Li-Quan Zhang; Lin Yuan (Estuaries and Coasts, 2015)

Inhibition of acid-sensing ion channel 1a in hepatic stellate cells attenuates PDGF-induced activation of HSCs through MAPK pathway - Fan-rong Wu; Chun-xiao Pan; Chao Rong; Quan Xia; Feng-lai Yuan; Jie Tang; Xiao-yu Wang; Nan Wang; Wen-lin Ni; Fei-hu Chen (Molecular and Cellular Biochemistry, 2014)

Non-pulmonary vein foci induced before and after pulmonary vein isolation in patients undergoing ablation therapy for paroxysmal atrial fibrillation: incidence and clinical outcome - Hui Cheng; Yin-yin Dai; Ru-hong Jiang; Qiang Liu; Ya-xun Sun; Jian-wei Lin; Zu-wen Zhang; Shi-quan Chen; Jun Zhu; Xia Sheng; Chen-yang Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

The phosphorylation of an actin depolymerizing factor by a calcium-dependent protein kinase regulates cotton fiber elongation - Quan-Sheng Huang; Xun-Ji Chen; Jian-Ping Li; Xiao-Yan Hao; Guo Chen; Zumuremu; Lin Shao (Acta Physiologiae Plantarum, 2014)

Typhoon-enhanced upwelling and its influence on fishing activities in the southern East China Sea - Yi Chang; Jui-Wen Chan; Yuan-Chao Angelo Huang; Wei-Quan Lin; Ming-An Lee; Kuo-Tien Lee; Cheng-Hsin Liao; Kae-Yih Wang; Yi-Chun Kuo (International Journal of Remote Sensing, 2014)

Genetic manipulation of a transcription-regulating sequence of porcine reproductive and respiratory syndrome virus reveals key nucleotides determining its activity - Haihong Zheng; Keyu Zhang; Xing-Quan Zhu; Changlong Liu; Jiaqi Lu; Fei Gao; Yan Zhou; Hao Zheng; Tao Lin; Liwei Li; Guangzhi Tong; Zuzhang Wei; et al. (Archives of Virology, 2014)

Migration of Ti from nano-TiO 2 -polyethylene composite packaging into food simulants - Qin-Bao Lin; He Li; Huai-Ning Zhong; Quan Zhao; Da-Hui Xiao; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2014)

Expression of bone morphogenetic protein 2, 4, and related components of the BMP signaling pathway in the mouse uterus during the estrous cycle - Yan Li; Quan-wei Wei; Jian-gang Feng; Mu-lin Xu; Rui-hua Huang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2014)

Differential Regulation of Lipid Metabolism Genes in the Brain of Acetylcholinesterase Knockout Mice - Huang-Quan Lin; Yan Wang; Kam-Leung Chan; Tsz-Ming Ip; Chi-Cheong David Wan (Journal of Molecular Neuroscience, 2014)

Gas outburst affected by original rock stress direction - Wei Yang; Bai-quan Lin; Jiang-tao Xu (Natural Hazards, 2014)

The rice OsDG2 encoding a glycine-rich protein is involved in the regulation of chloroplast development during early seedling stage - Quan Jiang; XiaoJing Ma; XiaoDi Gong; JianHui Zhang; Sheng Teng; JianLong Xu; DongZhi Lin; YanJun Dong (Plant Cell Reports, 2014)

BODIPY Fluorescent Chemosensor for Cu2+ Detection and Its Applications in Living Cells: Fast Response and High Sensitivity - Li Quan; Tingting Sun; Wenhai Lin; Xingang Guan; Min Zheng; Zhigang Xie; Xiabin Jing (Journal of Fluorescence, 2014)

Determinants of public goods investment in rural communities in mountainous areas of Sichuan Province, China - Shi-li Guo; Shao-quan Liu; Ren-fu Luo; Lin-xiu Zhang (Journal of Mountain Science, 2014)

Erratum to: Bacillus bingmayongensis sp. nov., isolated from the pit soil of Emperor Qin’s Terra-cotta warriors in China - Bo Liu; Guo-Hong Liu; Gui-Ping Hu; Cetin Sengonca; Nai-Quan Lin; Jian-Yang Tang; Wei-Qi Tang; Ying-Zhi Lin (Antonie van Leeuwenhoek, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

The effects of shRNA-mediated gene silencing of transcription factor SNAI1 on the biological phenotypes of breast cancer cell line MCF-7 - Yan Lu; Lina Yu; Minlan Yang; Xiangshu Jin; Zhijing Liu; Xiaowei Zhang; Liping Wang; Dongjing Lin; Yuanyuan Liu; Min Wang; Chengshi Quan (Molecular and Cellular Biochemistry, 2014)

Production of Autopolyploid Lowland Switchgrass Lines Through In Vitro Chromosome Doubling - Zhiyong Yang; Zhengxing Shen; Hannah Tetreault; Loretta Johnson; Bernd Friebe; Taylor Frazier; Lin-kai Huang; Caitlin Burklew; Xin-Quan Zhang; Bingyu Zhao (BioEnergy Research, 2014)

Bacillus bingmayongensis sp. nov., isolated from the pit soil of Emperor Qin’s Terra-cotta warriors in China - Bo Liu; Guo-Hong Liu; Gui-Ping Hu; Sengonca Cetin; Nai-Quan Lin; Jian-Yang Tang; Wei-Qi Tang; Ying-Zhi Lin (Antonie van Leeuwenhoek, 2014)

Molecular basis for insecticide‐enhanced thermotolerance in the brown planthopper N ilaparvata lugens S tål ( H emiptera: D elphacidae) - Lin‐Quan Ge; Liu‐Juan Huang; Guo‐Qin Yang; Qi‐Sheng Song; David Stanley; G. M. Gurr; Jin‐Cai Wu (Molecular Ecology, 2013)
Climate change is likely to have marked ecological effects on terrestrial ecosystems, including the activities of insect pests. Most attention has focused on the increasing geographical ranges of pests; however, if extrinsic factors enhance their thermotolerance, populations may express increased voltinism and longer daily and annual activity periods. These changes in pest populations have the potential for severe consequences, including increased crop losses and decreased food security at the global level. The brown planthopper ( BPH ) Nilaparvata lugens Stål (Hemiptera: Delphacidae) is a serious pest of rice crops in temperate and tropical regions of Asia. It is often present in rice microclimates at temperatures close to its maximum thermotolerance. Recent BPH outbreaks in tropical Asia are considered to be associated with excess use of pesticides and increasing temperature. This study tested whether exposure to sublethal concentrations of triazophos (tzp), an insecticide widely used in Asian rice production, enhances thermotolerance of BPH . Tzp exposure (40 ppm at 40 °C) significantly decreased mortality (from 94% in controls to 50% at 48 h post‐treatment) and increased lethal mean time ( LT 50 ) of adults by 17.2 h. To investigate the underlying molecular mechanism of this tzp‐enhanced thermotolerance, we selected Hsp70 and Arginine kinase (Argk) for detailed study. Transcripts encoding both proteins in third‐instar nymphs and brachypterous adult females were up‐regulated, compared with controls, after exposure to tzp. RNA i silencing of both genes demonstrated that Hsp70 and Argk are essential for survival and tzp‐increased thermotolerance. We propose that tzp induces thermotolerance in BPH s by increasing the expression of genes that act in cell protection mechanisms. The significance of our proposal relates to the importance of understanding the influence of sublethal concentrations of insecticides on pest biology. In addition to its influence on thermotolerance, tzp also enhances BPH reproduction. We infer that exposure to a pesticide stressor can produce cross‐tolerance, that is, increased tolerance to one stressor also increases tolerance to other stressors, including temperature. Aside from needing a better understanding of these effects in nature and in other pest/cropping systems, we suggest that pest management programmes can be improved with better understanding of the influences of stressors, including increased environmental temperatures and sublethal concentrations of insecticides, on pest biology.

The short chain cell-permeable ceramide (C6) restores cell apoptosis and perifosine sensitivity in cultured glioblastoma cells - Li-sen Qin; Zheng-quan Yu; Shi-ming Zhang; Guan Sun; Jian Zhu; Jin Xu; Jun Guo; Lin-shan Fu (Molecular Biology Reports, 2013)

Niche Divergence Among Sex and Age Classes in Black-and-White Snub-nosed Monkeys (Rhinopithecus bieti) - Yi Wan; Rui-Chang Quan; Guo-Peng Ren; Lin Wang; Yong-Cheng Long; Xiao-Hu Liu; Jian-Guo Zhu (International Journal of Primatology, 2013)

In vitro antifungal activity of antifungalmycin 702, a new polyene macrolide antibiotic, against the rice blast fungus Magnaporthe grisea - Zhi-Qiang Xiong; Xiao-Rong Tu; Sai-Jin Wei; Lin Huang; Xun-Hang Li; Hui Lu; Guo-Quan Tu (Biotechnology Letters, 2013)

Time-dependent regulation of neuregulin-1β/ErbB/ERK pathways in cardiac differentiation of mouse embryonic stem cells - Ming Chen; Lin-Lin Bi; Zhi-Quan Wang; Fang Zhao; Xue-Dong Gan; Yang-Gan Wang (Molecular and Cellular Biochemistry, 2013)

Mapping of QTL lengthening the latent period of Puccinia striiformis in winter wheat at the tillering growth stage - Wei Quan; Guangliang Hou; Jiang Chen; Ziyi Du; Feng Lin; Yan Guo; Song Liu; Zhongjun Zhang (European Journal of Plant Pathology, 2013)

Isolation and characterization of novel ginsenoside-hydrolyzing glycosidase from Microbacterium esteraromaticum that transforms ginsenoside Rb2 to rare ginsenoside 20(S)-Rg3 - Lin-Hu Quan; Chao Wang; Yan Jin; Ting-Rui Wang; Yeon-Ju Kim; Deok Chun Yang (Antonie van Leeuwenhoek, 2013)

Microbial transformation of ginsenoside Rb1 to compound K by Lactobacillus paralimentarius - Lin-Hu Quan; Yeon-Ju Kim; Guan Hao Li; Kwang-Tea Choi; Deok-Chun Yang (World Journal of Microbiology and Biotechnology, 2013)

Chemistry, bioactivity and quality control of Dendrobium, a commonly used tonic herb in traditional Chinese medicine - Jun Xu; Quan-Bin Han; Song-Lin Li; Xiao-Jia Chen; Xiao-Ning Wang; Zhong-Zhen Zhao; Hu-Biao Chen (Phytochemistry Reviews, 2013)

Molecular detection and genomic characterization of Torque teno sus virus 1 and 2 from domestic pigs in central China - Kun Li; Lin-Qing Wang; Yu-Yang Wu; An-Jun Chao; Quan-Wei Lu; Zhan-Yong Wei; Bao-An Cui; Hong-Ying Chen (Virus Genes, 2013)

Levosimendan versus dobutamine in critically ill patients: a meta-analysis of randomized controlled trials - Xuan Huang; Shu Lei; Mei-fei Zhu; Rong-lin Jiang; Li-quan Huang; Guo-lian Xia; Yi-hui Zhi (Journal of Zhejiang University-SCIENCE B, 2013)

Matrine suppresses expression of adhesion molecules and chemokines as a mechanism underlying its therapeutic effect in CNS autoimmunity - Quan-Cheng Kan; Lin Zhu; Nan Liu; Guang-Xian Zhang (Immunologic Research, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

hPNAS-4 inhibits proliferation through S phase arrest and apoptosis: underlying action mechanism in ovarian cancer cells - Lei Li; Den-bang Chen; Chao Lin; Kang Cao; Yang Wan; Xin-yu Zhao; Chun-lai Nie; Zhu Yuan; Yu-quan Wei (Apoptosis, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

The dissection and SSR mapping of a high-temperature adult-plant stripe rust resistance gene in American spring wheat cultivar Alturas - Lei Zhao; Jing Feng; Chun-Yu Zhang; Xiao-Dan Xu; Xian-Ming Chen; Quan Sun; Qing Miao; Shi-Chang Xu; Feng Lin (European Journal of Plant Pathology, 2012)

Haplotype variations of gene Ppd-D1 in Aegilops tauschii and their implications on wheat origin - Lin Huang; Qing Wang; Lian-Quan Zhang; Zhong-Wei Yuan; Ji-Rui Wang; Huai-Gang Zhang; You-Liang Zheng; Deng-Cai Liu (Genetic Resources and Crop Evolution, 2012)

Prevention and treatment of allergic inflammation by an Fcγ-Der f2 fusion protein in a murine model of dust mite-induced asthma - Li-hui Lin; Ping Zheng; John W. M. Yuen; Juan Wang; Juan Zhou; Cun-quan Kong; Xia Peng; Jia Li; Li Li (Immunologic Research, 2012)

Biotransformation of ginsenosides Re and Rg1 into ginsenosides Rg2 and Rh1 by recombinant β-glucosidase - Lin-Hu Quan; Jin-Woo Min; Subramaniyam Sathiyamoorthy; Dong-Uk Yang; Yeon-Ju Kim; Deok-Chun Yang (Biotechnology Letters, 2012)

SIRT1 is required for long-term growth of human mesenchymal stem cells - Hong-Feng Yuan; Chao Zhai; Xin-Long Yan; Dan-Dan Zhao; Jing-Xue Wang; Quan Zeng; Lin Chen; Xue Nan; Li-Juan He; Si-Ting Li; Wen Yue; Xue-Tao Pei (Journal of Molecular Medicine, 2012)

Cholecystectomy and risk of pancreatic cancer: a meta-analysis of observational studies - Genlai Lin; Zhaochong Zeng; Xiaolin Wang; Zheng Wu; Jian Wang; Chenggang Wang; Qiao Sun; Yixing Chen; Hongbo Quan (Cancer Causes & Control, 2012)

Interleukin 29 enhances expression of toll receptor 3 and mediates antiviral signals in human keratinocytes - Sheng-Quan Zhang; Zheng Zhang; Xin Luo; Sen Yang; Yu Chai; Hai-Liang Huang; Xian-Yong Yin; Dao-Jun Hu; Chun-Jun Yang; Jun-Lin Liu; Xue-Jun Zhang (Inflammation Research, 2011)

Positive allelopathic stimulation and underlying molecular mechanism of achyranthe under continuous monoculture - Zhen-Fang Li; Zi-Guan Zhang; Dong-Feng Xie; Lin-Quan Dai; Lan-Fang Zhu; Ji Li; Zong-Quan Liu; Yan-Qiu Yang; Lin-Kun Wu; Mu-Ji Huang; Zhong-Yi Zhang; Wen-Xiong Lin (Acta Physiologiae Plantarum, 2011)

Tetanic contractions impair sarcomeric Z-disk of atrophic soleus muscle via calpain pathway - Xiao-Wu Ma; Quan Li; Peng-Tao Xu; Lin Zhang; Hui Li; Zhi-Bin Yu (Molecular and Cellular Biochemistry, 2011)

Characteristics of petroleum hydrocarbons in surficial sediments from the Songhuajiang River (China): spatial and temporal trends - Wei Guo; Mengchang He; Zhifeng Yang; Chunye Lin; Xiangchun Quan (Environmental Monitoring and Assessment, 2011)

Distribution patterns of nitroaromatic compounds in the water, suspended particle and sediment of the river in a long-term industrial zone (China) - Bin Men; Haozheng Wang; Mengchang He; Chunye Lin; Xiangchun Quan (Environmental Monitoring and Assessment, 2011)

Development and characterization of wheat-Psathyrostachys huashanica partial amphiploids for resistance to stripe rust - Yi Wang; Quan Xie; Kangyu Yu; Vaino Poysa; Lijuan Lin; Houyang Kang; Xing Fan; Lina Sha; Haiqin Zhang; Yonghong Zhou (Biotechnology Letters, 2011)

Molecular tagging of a stripe rust resistance gene in Aegilops tauschii - Lin Huang; Lian-Quan Zhang; Bao-Long Liu; Ze-Hong Yan; Bo Zhang; Huai-Gang Zhang; You-Liang Zheng; Deng-Cai Liu (Euphytica, 2011)

The complete mitochondrial genomes of three cestode species of Taenia infecting animals and humans - Guo-Hua Liu; Rui-Qing Lin; Ming-Wei Li; Wei Liu; Yi Liu; Zi-Guo Yuan; Hui-Qun Song; Guang-Hui Zhao; Kou-Xing Zhang; Xing-Quan Zhu (Molecular Biology Reports, 2011)

The detection of “Candidatus Mycoplasma haemobos” in cattle and buffalo in China - Q. L. Su; H. Q. Song; R. Q. Lin; Z. G. Yuan; J. F. Yang; G. H. Zhao; W. Y. Huang; Xing Quan Zhu (Tropical Animal Health and Production, 2010)

Molecular phylogeny of Ranunculaceae based on rbc L sequences - Ying-fan Cai; Sheng-wei Li; Min Chen; Ming-feng Jiang; Yi Liu; Yong-fang Xie; Quan Sun; Huai-zhong Jiang; Neng-wen Yin; Ling Wang; Rui Zhang; Cheng-lin Huang; et al. (Biologia, 2010)

Genetic characterization of ticks from southwestern Romania by sequences of mitochondrial cox1 and nad5 genes - Lidia Chitimia; Rui-Qing Lin; Iustin Cosoroaba; Xiang-Yun Wu; Hui-Qun Song; Zi-Guo Yuan; Xing-Quan Zhu (Experimental and Applied Acarology, 2010)

Rubellimicrobium roseum sp. nov., a Gram-negative bacterium isolated from the forest soil sample - Yan-Ru Cao; Yi Jiang; Qian Wang; Shu-Kun Tang; Wen-Xiang He; Quan-Hong Xue; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2010)

Erratum to: AtCPK6, a functionally redundant and positive regulator involved in salt/drought stress tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xiao-Fen Jin; Feng Gao; Xiao-Yan Fu; Xi-Lin Hou; Quan-Hong Yao (Planta, 2010)

Responses of soil chemical and biological properties to nitrogen addition in a Dahurian larch plantation in Northeast China - Ya-Lin Hu; De-Hui Zeng; Yun-Xia Liu; Yu-Lan Zhang; Zhen-Hua Chen; Zheng-Quan Wang (Plant and Soil, 2010)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

A new antitumour ansamitocin from Actinosynnema pretiosum - Guo-Zhu Wei; Lin-Quan Bai; Tao Yang; Juan Ma; Ying Zeng; Yue-Mao Shen; Pei-Ji Zhao (Natural Product Research, 2010)

AtCPK6, a functionally redundant and positive regulator involved in salt/drought stress tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xiao-Fen Jin; Feng Gao; Xiao-Yan Fu; Xi-Lin Hou; Quan-Hong Yao (Planta, 2010)

Occurrence of Aliphatic Hydrocarbons in Water, Suspended Particulate Matter and Sediments of Daliao River System, China - W. Guo; M. C. He; Z. F. Yang; C. Y. Lin; X. C. Quan (Bulletin of Environmental Contamination and Toxicology, 2010)

Allopatric divergence and phylogeographic structure of the plateau zokor ( Eospalax baileyi ), a fossorial rodent endemic to the Qinghai–Tibetan Plateau - Li‐Zhou Tang; Liu‐Yang Wang; Zhen‐Yuan Cai; Tong‐Zuo Zhang; Hai‐Xin Ci; Gong‐Hua Lin; Jian‐Ping Su; Jian‐Quan Liu (Journal of Biogeography, 2010)
Aim Most species of temperate regions are believed to have shifted to lower latitudes or elevations during the glacial periods of the Quaternary. In this study we test whether this phylogeographic assumption is also true for the plateau zokor ( Eospalax baileyi ), a fossorial rodent endemic to the climate‐sensitive Qinghai–Tibetan Plateau (QTP), which ranges in elevation from 2600 to 4600 m. Location The QTP of western China. Methods Phylogeographic analyses were conducted based on the mitochondrial cytochrome b gene sequences of 193 individuals from 20 populations over the entire range of the species. Results A total of 54 haplotypes identified in the present study clustered into four geographically correlated clades located in the interior of the QTP (clade A) and at the plateau edge (B, C and D). Molecular calibrations suggest that the interior plateau (A) and plateau‐edge (B–D) clades diverged at 1.2 Ma and that the three plateau‐edge clades diverged between 0.85 and 0.80 Ma. These estimates are concordant with diastrophism and glaciation events in the QTP. Coalescent tests rejected both the hypothesis that all current populations originated from a single refugium at a low elevation during the Last Glacial Maximum (LGM) and the hypothesis that the two lineages diverged during the LGM. The tests instead supported the hypothesis that there were four refugia during the LGM, and that the four clades diverged prior to the late Pleistocene. Main conclusions Our results suggest that Quaternary diastrophisms and glaciations repeatedly promoted allopatric divergence of the plateau zokor into geographical clades, and that these regional clades subsequently persisted at high elevations, rather than migrating to the low‐elevation plateau edge during subsequent glacial ages.

Cyanobacteria MT gene SmtA enhance zinc tolerance in Arabidopsis - Jing Xu; Yong-Sheng Tian; Ri-He Peng; Ai-Sheng Xiong; Bo Zhu; Xi-Lin Hou; Quan-Hong Yao (Molecular Biology Reports, 2010)

Fabrication of a Novel Core-Shell Gene Delivery System Based on a Brush-Like Polycation of α, β–Poly (L-Aspartate-Graft-PEI) - Jia-Hui Yu; Ji-Shan Quan; Jung-Taek Kwon; Cheng-Xiong Xu; Bo Sun; Hu-Lin Jiang; Jae-Woon Nah; Eun-Mi Kim; Hwan-Jeong Jeong; Myung-Haing Cho; Chong-Su Cho (Pharmaceutical Research, 2009)

KIFC1 participates in acrosomal biogenesis, with discussion of its importance for the perforatorium in the Chinese mitten crab Eriocheir sinensis - Keming Yu; Lin Hou; Jun-Quan Zhu; Xue-Ping Ying; Wan-Xi Yang (Cell and Tissue Research, 2009)

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

A Comparative Analysis of Molecular Diversity of Erect Milkvetch (Astragalus adsurgens) Germplasm from North China Using RAPD and ISSR Markers - Lin-kai Huang; Zhi-hong Chen; Xin-quan Zhang; Zhi-gang Wang; Chou-sheng Liu (Biochemical Genetics, 2009)

A new species of Rhinogobius (Teleostei: Gobiidae) from the Feiyunjiang Basin in Zhejiang Province, China - Jin-Quan Yang; Han-Lin Wu; I-Shiung Chen (Ichthyological Research, 2008)

Continuous removal of aromatic hydrocarbons by an AF reactor under denitrifying conditions - Xiangchun Quan; Wenyan Wang; Zhifeng Yang; Chunye Lin; Mengchang He (World Journal of Microbiology and Biotechnology, 2007)

Monitoring and Assessment of Persistent Organochlorine Residues in Sediments from the Daliaohe River Watershed, Northeast of China - Haozheng Wang; Mengchang He; Chunye Lin; Xiangchun Quan; Wei Guo; Zhifeng Yang (Environmental Monitoring and Assessment, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The spectral responses of a submerged plant Vallisneria spiralis with varying biomass using spectroradiometer - Lin Yuan; Li-Quan Zhang (Hydrobiologia, 2007)

Isolated and characterization of a cDNA encoding ethylene-responsive element binding protein (EREBP)/AP2-type protein, RCBF2, in Oryza sativa L. - Jin-Ge Liu; Zhen Zhang; Qiu-Lin Qin; Ri-He Peng; Ai-Sheng Xiong; Jian-Min Chen; Fang Xu; Hong Zhu; Quan-Hong Yao (Biotechnology Letters, 2006)

Roots of pioneer trees in the lower sub-tropical area of Dinghushan, Guangdong, China - Yan-ru Hao; Shao-lin Peng; Jiang-ming Mo; Xin-wei Liu; Zhuo-quan Chen; Kai Zhou; Jin-rong Wu (Journal of Zhejiang University-SCIENCE B, 2006)

Protection against translocating Salmonella typhimurium infection in mice by feeding the immuno-enhancing probiotic Lactobacillus rhamnosus strain HN001 - Harsharnjit S. Gill; Quan Shu; Hai Lin; Kay J. Rutherfurd; Martin L. Cross (Medical Microbiology and Immunology, 2001)

Stimulation effect of gibberellic acid short-term treatment on leaf photosynthesis related to the increase in Rubisco content in broad bean and soybean - Lin Yuan; Da-Quan Xu (Photosynthesis Research, 2001)